Multi-scroll generation mechanism, dynamic analysis, and DSP implementation of a dual-memristor-coupled Sprott-C system - Yichen Bi; Shuhan Yang; Xianying Xu; Santo Banerjee; Jun Mou (Cognitive Neurodynamics, 2026)

Endophytic fungi mediate litter decomposition dynamics through microbial interactions and temporal shifts - Yuan-Qi Zhao; Fu-Sen Nan; Xiao-Qian Yang; Jian-Fei Yu; Han-Yue Bi; Si-Jun Duan; Xin-Yue Wang; Tian-Ci Chen; Qin-Jiang Mao; Xiao-Bo Wang (Soil Biology and Biochemistry, 2026)

Physical consumption data reveals hidden carbon inequalities beyond monetary-based accounting - Yuru Guan; Yang Wang; Ruoqi Li; Ye Hang; Yuli Shan; Miaomiao Liu; Peipei Tian; Jun Bi; David Andersson; Klaus Hubacek (Sustainable Production and Consumption, 2026)

Conversion of biomass ash into cementitious materials with dicalcium silicate for soil stabilization - Qiyong Zhang; Zefa Lu; Jun Bi; Xiaoniu Yu; Bingxiang Yuan; Linyong Cui (Chemical Engineering Journal, 2026)

Facile fabrication of robust hydrophobic-oleophilic aerogel for oil/water separation and thermal management - Dongwei Bi; Shiyao Ma; Yitong Chen; Zhen Yang; Xiao Han; Yuedan Wang; Wenfu Yu; Yulong Zhang; Yueyang Hong; Jun Yan; Huimin Zhang (Environmental Research, 2026)

Supramolecular assembly-driven N-type surface reconstruction for efficient and scalable perovskite solar cells - Haijun Wang; Pengjie Zhang; Jin Wang; Weihui Bi; Po-Chuan Yang; Shen Xing; Mengyuan Li; Jun Lv; Yufei Zhong (Chemical Engineering Journal, 2026)

PTPσ mediates the integration of grafted neuronal tissueoids with host neural pathways after complete spinal cord injury - Rui Mao; Yuan-Huan Ma; Jin-Yuan Xiao; Qing-Shuai Wei; Yin-Chun Zhao; Qi-Xing Hu; Hou-Ge Li; Ke-Jun Zhang; Lai-Jian Wang; Hui-Juan Shi; Li-Zhi Peng; Jun-Hua Wang; et al. (Science China Life Sciences, 2026)

Corrigendum to “A phospho-switch centered on OsAHL23 orchestrates immune homeostasis in rice” [Sci. Bull. 71(11) (2026), 2701-2705] - Zhaotang Ma; Qi He; Haicheng Liao; Junjie Yin; Xiaobo Zhu; Xiang Lu; Li Song; Long Wang; Hai Qing; Yu Fang; Kangjian Niu; Langqing Chen; et al. (Science Bulletin, 2026)

Thermal damage thresholds of soil resources: implications for targeted post-fire land management - Qiyong Zhang; Shiji Wang; Xian Li; Anjun Li; Bingxiang Yuan; Jun Bi (Environment, Development and Sustainability, 2026)

Heat transfer analysis of thawing behavior in artificially frozen subway cross passage under seepage conditions - Yunxi Han; Yupeng Shen; Xin Liu; Jun Zhi; Weigang Bi (Tunnelling and Underground Space Technology, 2026)

Genomic and genetic insights into the divergence between indica and japonica rice - Xiangxi Zhuansun; Wenlong Guo; Siqi Xia; Jun Shu; Kai Wang; Qiyu Zhang; Hao Wen; Lina Du; Siyu Wen; Ge Gao; Junran Wang; Dan Wang; et al. (Science Bulletin, 2026)

Study on the Ce–MnO2 catalyst prepared by a mechanochemical method to enhance its synergistic removal of NOx and VOCs - Ao Zhang; Jun Liu; Shilin Bi; Yunlan Sun; Duanhe Zhao; Daxiang Hou; Jiaxin Wang; Minggao Xu; Baozhong Zhu (Fuel, 2026)

A layered approach to secure the safety and therapeutic efficacy of hiPSC-derived functionalized neuronal tissueoid for repair after complete spinal cord lnjury in rats - Qing-shuai Wei; Quan-ying Xing; Yuan-huan Ma; Ke-jun Zhang; Wen-tao Ma; Mei-ling Zhang; Hui-juan Shi; Li-zhi Peng; Jun-hua Wang; Qi-xing Hu; Hou-ge Li; Ying Liu; et al. (Chemical Engineering Journal, 2026)

Zircon–monazite geochronology and zircon Hf–O isotopes of Ediacaran–Cambrian paragneiss from the Mashan Complex, Jiamusi Block, NE China: implications for sedimentary–metamorphic–tectonic evolution - Guan-Ying Yu; Hao Yang; Jia-Hao Jing; Zheng Ji; Yan-Long Zhang; Jun-Hui Bi; Wen-Chun Ge (International Geology Review, 2026)

A phospho-switch centered on OsAHL23 orchestrates immune homeostasis in rice - Zhaotang Ma; Qi He; Haicheng Liao; Junjie Yin; Xiaobo Zhu; Xiang Lu; Li Song; Long Wang; Hai Qing; Yu Fang; Kangjian Niu; Langqing Chen; et al. (Science Bulletin, 2026)

Integrating health and climate priorities in coal retirement strategies for China: a policy-adaptive approach - Jinyang Huang; Jiacong Cai; Zhan Zhao; Jianxun Yang; Haozhe Yang; Miaomiao Liu; Wen Fang; Zongwei Ma; Jun Bi (Resources, Conservation and Recycling, 2026)

Non-negligible disparities in source-specific ambient PM2.5 across economic groups over space and time in China - Yanchuan Shao; Zongwei Ma; Jianxun Yang; Miaomiao Liu; Wen Fang; Matthew Adams; Jun Bi (Journal of Hazardous Materials, 2026)

Microenvironment responsive copper-polyphenol nanozyme hybrid hydrogel with NO/O2 release for healing diabetic infected wounds via immunomodulation and angiogenesis - Changyuan He; Ruiqi Liu; Siwei Bi; Li Zhang; Jun Gu; Bin Yan (Chemical Engineering Journal, 2026)

Interpretable machine learning for ambient air pollution modeling: A systemic review - Yanchuan Shao; Riyang Liu; Shenyuan Huang; Wen Fang; Jianxun Yang; Miaomiao Liu; Jun Bi; Zongwei Ma (Atmospheric Research, 2026)

Hydrodynamic impacts of floating-raft aquaculture in the northern yellow sea: modeling and field experiments - Xiaomeng Fu; Jie Tian; Ming Li; Yuan Zhang; Junru Guo; Jun Song; Yang Ding; Congcong Bi (Ocean Dynamics, 2026)

Ship hydrodynamic optimization for minimum resistance through an improved grey wolf algorithm and ship model experimental verification - Jie Liu; Li-fen Hu; Bao-ji Zhang; Yong-yi Jiang; Jun-ying Bi; Ying-kai Dong; Guo-hua Yan (Ocean Engineering, 2026)

Biosynthesis of active small molecule prenylsalidroside a and its anti-inflammatory activity - Jia-Hao Xue; Hua-Jin Yu; Long-Jun Li; Gui-Hu Lu; Pei-Shan Li; Xia Cheng; Qi Luo; Wei Wu; Zhong-Sheng Bi (Natural Product Research, 2026)

Discrete element modeling and experimental validation of the multi-scale based coronal tea plant root-soil complex - Kuan Qin; Junjie Lu; Jin Zhang; Chengmao Cao; Zichen Huang; Xuechen Zhang; Weidong Gao; Xu Zhu; Kang Xue; Liwei Wang; Zhengmin Wu; Haijun Bi; et al. (Computers and Electronics in Agriculture, 2026)

Immunogenicity and safety of an Escherichia coli-produced 9-valent HPV vaccine in adolescents aged 9 to 17 compared with young women - Yulin Jing; Xiaowen Hu; Li Zhang; Jiangyahui Wang; Fei Yang; Rong Wang; Ying Jiang; Lingling Nie; Zhongqiang Jin; Xuecheng Liu; Sihai Li; Chao Du; et al. (Science Bulletin, 2026)

Mechanistic insights into the enhanced degradation of hydroxychloroquine by singlet oxygen in PMS and PMS/Cl2 systems: A comparative study - Zi-Han Feng; Zhen-Zhen Li; Dong-Su Bi; Fu-Xiang Tian; Ling-Yao Meng; Yan-Ting Jia; Yu-Qiong Gao; Xiao-Jun Hu (Journal of Environmental Management, 2026)

Experimental study on the physical, mechanical, and microstructural properties of geopolymer-stabilized soils exposed to different curing temperature conditions - Jun Bi; Yuxuan Pan; Ruiqiang Bai; Qiyong Zhang; Xiao Jiang; Song Xu; Zhenyu Liu (Journal of Environmental Chemical Engineering, 2026)

Investigation on the unfrozen water content and freezing point models of saline soils - Guoxu Wang; Jun Bi (Journal of Environmental Chemical Engineering, 2026)

Prediction of overpressure from hydrogen cloud explosions: A study from open space to hydrogen refueling and filling station scenarios - Qiuhong Wang; Bin Peng; Jun Deng; Wei Gao; Jianyi Chen; Hongxiang Wan; Mingshu Bi; Ran Liu; Chaoyuan Hu (Process Safety and Environmental Protection, 2026)

Enhanced sequential soil moisture estimation using an ensemble deep learning filter without linear-Gaussian constraints - Tuantuan Zhang; Jianxia Chang; Jiangjiang Zhang; Quanxi Shao; Ranjan Sarukkalige; Zengliang Luo; Chenglin Bi; Jun Wang; Yiming Hu; Binquan Li; Zhongmin Liang (Journal of Hydrology, 2026)

Landscape of environmental pollutant–driven alterations of nucleic acid modifications in hepatoma cells - Tian Feng; Yao-Hua Gu; Qiu-Shuang Hu; Neng-Bin Xie; Shu-Yi Gu; Fang-Yin Gang; Jun Xiong; Bi-Feng Yuan (Journal of Hazardous Materials, 2026)

Coal tar phenolic DES back-extraction study based on Hansen parameters: A combined experimental and computational approach - Dezhi Cao; Dingkai Hu; Wenna Wang; Xinyue Lin; Xinpeng Bi; Jun Tang; Qiang Wang (Fuel, 2026)

Effects of metals on thermal oxidation of jet fuel and mitigation strategies - Bowang Lu; Xiaoyong Fan; Dong Li; Jun Yang; Long Yan; Bo Yang; Guanghui Pang; Jian Li; Bi Chen (Fuel, 2026)

Exploring homogeneous learnware market for PM2.5 prediction: A case study in the Yangtze River Delta region of China - Yuchen Zhang; Yanchuan Shao; Riyang Liu; Jun Bi; Zongwei Ma (Atmospheric Pollution Research, 2026)

Biosynthesis of the fragrance compound cinnamyl isobutyrate in Escherichia coli - Moshi Liu; Jun Tang; Yanqiao Xue; Huiping Bi; Tao Liu (Biotechnology Letters, 2026)

Study on Hydrodynamics and Water Exchange Capacity in the Changhai Sea Area Based on the FVCOM Model - Minghao Yang; Jun Song; Congcong Bi; Dawei Jiang; Ming Li; Yuan Zhang; Junru Guo; Jie Tian; Qian Sun (Journal of Marine Science and Engineering, 2026)
Water exchange capacity is critical for maintaining marine environmental quality and supporting the sustainable development of aquaculture. This study applies a high-resolution three-dimensional FVCOM hydrodynamic model coupled with the DYE-RELEASE module. The model was validated against tidal, current, and thermohaline observations. Water residence time (Tre) was used as the primary evaluation metric, supplemented by analyses of residual circulation, material diffusion, and regional variability, to systematically quantify the water exchange mechanisms and seasonal variations in the coastal waters of Changhai County under the combined influence of tides, wind forcing, and thermohaline conditions. Results show that overall residual currents in Changhai County are weak (average velocity: 0.032 m s−1). However, local circulations and stagnation zones frequently develop near islands and channels, strongly influencing material diffusion. In summer, water exchange is primarily controlled by thermohaline effects, which strengthen density stratification, suppress vertical mixing, and modify circulation patterns, thereby reducing the efficiency of tide-driven exchange. Water exchange is weakest near Guanglu Island (46.6–48.6 d) and strongest near Haiyang Island (13–14 d). In winter, wind forcing dominates, enhancing vertical mixing and accelerating water renewal. Residence time in the Changshan Archipelago–Guanglu Island region decreases by 30–50% compared with summer. Overall, winter water renewal is 15–25% more efficient than in summer. This study demonstrates that water exchange in Changhai County is regulated by the combined effects of tides, wind forcing, and thermohaline dynamics. The identified spatial heterogeneity and seasonal characteristics provide a scientific basis for optimizing aquaculture planning and mitigating marine environmental risks.

Human-induced changes in fluvial regimes for organic carbon supply and burial off the Yellow River Estuary - Li Jiang; Limin Hu; Naishuang Bi; Jinya Xu; Jun Ye; Lin Liu; Fudong Lin; Weini Chong; Jiazong Du; Xiao Wu; Houjie Wang (Water Research, 2026)

Dissection of the genetic basis of 1392 rice landraces and 770 hybrid combinations reveals great potential of rice landraces in hybrid rice improvement - Yinting Wang; Zixuan Li; Bi Wu; Xueqiang Wang; Wenyan Yang; Danjing Lou; Jinyue Ge; Ziran Liu; Wenlong Guo; Neng Zhao; Jun Yang; Weiya Fan; et al. (Molecular Plant, 2026)

Promoting aerobic denitrification in the rhizosphere by vertical spatial stress: A strategy to enhance nitrogen conversion efficiency in constructed wetlands - Sheng-Jing Zhang; Hao-Qi Lu; Lei Yang; Li-De Wang; Bi-Han Zhang; Chao-Wen Deng; Jun Lan; Yong-Xiang Ren (Environmental Research, 2026)

Mechanistic investigation of NH3 and NO in toluene catalytic oxidation over manganese-iron ore catalyst: Synergistic and individual effects revealed by experiment and DFT - Shilin Bi; Jun Liu; Ao Zhang; Jiaxin Wang; Baozhong Zhu; Minggao Xu; Yunlan Sun (Journal of Environmental Chemical Engineering, 2025)

Toxicokinetics of typical halogenated organic pollutants (HOPs) in frogs (Rana tigrina cantor) via skin exposure and effects of hibernation - Ke-Lan Guan; Xiao-Jun Luo; Chu-Hong Zhu; Jian Guo; Yan-Hong Zeng; Bi-Xian Mai (Environmental Pollution, 2025)

Potential and applications of stable oxygen isotope chronologies for tree-ring dating in South Korea - En-Bi Choi; Jun-Hui Park; Masaki Sano; Takeshi Nakatsuka; Jeong-Wook Seo (Dendrochronologia, 2025)

Establishing ring width and cell chronologies for predicting future growth of Thuja koraiensis under climate change - Jun-Hui Park; En-Bi Choi; Ho-Young Lee; Jeong-Wook Seo (Dendrochronologia, 2025)

Tailoring nucleation and crystallization in perovskite solar cells and modules via spatially designed strong coordinating sites - Mengfan Ma; Pengjie Zhang; Peng Mao; Weihui Bi; Jun Lv; Mengyuan Li; Po-Chuan Yang; Zongbao Zhang; Yufei Zhong (Chemical Engineering Journal, 2025)

A neutron transport calculation approach via the coupling of 2D/1D and 3D SN nodal methods - Hongchun Wu; Shuaizheng Li; Jun Chen; Guangwen Bi; Zhouyu Liu; Sifan Zhang; Xinyu Zhou; Liangzhi Cao (Annals of Nuclear Energy, 2025)

A novel approach for emergency action planning based on functional modeling and reasoning - Jun Yang; Shuxin Bi; Yipeng Fan; Mengchu Song (Process Safety and Environmental Protection, 2025)

Sesamol inhibits fungal growth by destroying the redox dynamic equilibrium in Pestalotiopsis neglecta - Jing-Yu Ji; Li-Ying Huang; Bing Bi; Ya-Jun Wang; Jin-Yan Zhao; Sheng-Yu Zhang; Ze Wang; Shu-ming Cui; Qiao-ya Zhang; Guo-Cai Zhang (Physiological and Molecular Plant Pathology, 2025)

Machine learning decoding of electronic thresholds in prediction of oriented generation of solar-induced oxidative reactive species and antibiotics degradation - Hao Bi; Zhiruo Zhou; Qian Liu; Ran Zhao; Fangyuan Chen; Jun Zhang; Zhurui Shen (Journal of Hazardous Materials, 2025)

Circ-379-miR-3050-DNAH3/RNF8 axis modulates wing development in Aphis citricidus - Yu-Jing Liu; Jin-Ming Lu; Xiu-Cheng Xie; Qin-Qin Xu; Bi-Yue Ding; Jin-Jun Wang; Feng Shang (Insect Biochemistry and Molecular Biology, 2025)

A mechanistic perspective: How does tert-butylhydroquinone retain antioxidative efficacy in edible oils during storage? - Mengqi Xu; Yaxing Yu; Jun Li; Yanlan Bi; Jun Liu; Chenyu Fu (Food Chemistry, 2025)

Species- and sex-specific bioaccumulation, tissue-specific distribution, and maternal transfer of per- and polyfluoroalkyl substances in tiger frogs (Hoplobatrachus chinensis) and forest frogs (Rana chensinensis) - Chu-Hong Zhu; Xiao-Jun Luo; Xi Chen; Peng-Peng Chen; Ke Lan Guan; Yan-Hong Zeng; Bi-Xian Mai (Environmental Research, 2025)

Adapting to hypo-salinity: Molecular mechanisms in giant clams and symbionts with implications for coral reef resilience under climate change - Zhen Zhao; Xixi Duan; Tao Zhang; Siqi Bi; Zohaib Noor; Shuming Guo; Zonglu Wei; Yinjie Zhang; Yanping Qin; Haitao Ma; Ying Pan; Ziniu Yu; et al. (Environmental Research, 2025)

Smart dual-channel fluorescent sensor overcoming cross-interference: Visual detection of Cu(II) and doxycycline in multiple scenarios, and precise discrimination of tetracycline analogs - Yingqi Yuan; Liuqing Fu; Lina Zhang; Jun Xu; Ning Bi; Yongxin Li; Lei Jia (Chemical Engineering Journal, 2025)

Synergistic A-site engineering and B-site anchoring in photovoltaic perovskites renders efficient and stable solar cells - Runbo Zhao; Weihui Bi; Peng Mao; Jun Lv; Yang Po-Chuan; Mengyuan Li; Pengjie Zhang; Yingying Xu; Shen Xing; Yufei Zhong (Chemical Engineering Journal, 2025)

The novel selective HDAC1 inhibitor ZJH-1 exhibits potent antitumor activity in castration-resistant prostate cancer, potentially involving HSP90AA1 - Yizhong Bao; Jitao Li; Aokang zhang; Yixiu Ni; Mingjing Bi; Jun Chen (Chemico-Biological Interactions, 2025)

Effect of mixing and compaction methods on the physical properties, strength and microstructure of phase change material-modified soils under freeze-thaw process - Jun Bi; Yuxuan Pan; Wenxuan Mu; Mingyi Zhang; Guiyu Zhao; Haoxin Chen; Pengfei Liu (Cold Regions Science and Technology, 2025)

Experimental study and generalized predictive model of thermal conductivity of saline soil - Zhongrui Yan; Zhiliang Liu; Xusheng Wan; Jun Bi; Jun Diao; Yongqiang Cao (Bulletin of Engineering Geology and the Environment, 2025)

Biotransformation causes the sex-specific regulation of polychlorinated biphenyls during metamorphosis of silkworm (Bombyx mori) and their effect on the silkworm development - Xue-Meng Qi; Xiao-Jun Luo; Pei-Xin Su; Peng-Peng Chen; Qing-Rong Yang; Yan-Hong Zeng; Bi-Xian Mai (Journal of Hazardous Materials, 2025)

Mapping public behavioral intentions for mitigation and adaptation to air pollution in China - Yining Huang; Xiaohan Cui; Miaomiao Liu; Jianxun Yang; Wen Fang; Zongwei Ma; Jun Bi (Journal of Cleaner Production, 2025)

A bifunctional sensing platform integrated with gel beads-based sensor for ultrasensitive and point-of-care testing of tetracycline and Hg(II) - Xia Zhang; Lina Zhang; Jun Xu; Yingqi Yuan; Yongxin Li; Ning Bi; Lei Jia (Journal of Environmental Chemical Engineering, 2025)

Medical expenditures under climate change and SSP-informed physiological and socioeconomic scenarios in China - Dianyu Zhu; Miaomiao Liu; Yuli Shan; Ruoqi Li; Haofan Zhang; Yuan Li; Jun Bi; Klaus Hubacek (Global Environmental Change, 2025)

Effects of hibernation on the bioaccumulation and tissue distribution of per- and polyfluoroalkyl substances in frogs (Rana tigrina cantor) via skin exposure - Chu-Hong Zhu; Xiao-Jun Luo; Ke-Lan Guan; Jian Guo; Peng-Peng Chen; Xi Chen; Yan-Hong Zeng; Bi-Xian Mai (Environmental Pollution, 2025)

An antioxidative sodium alginate hybrid hydrogel with NIR-controlled NO releasing for diabetic wound healing via reduced inflammation and enhanced angiogenesis - Changyuan He; Siwei Bi; Li Zhang; Jun Gu; Bin Yan (Carbohydrate Polymers, 2025)

Recycling of sub-continental lithosphere during early ocean spreading revealed by Triassic trachytes in the central Tibetan Plateau - Zong-Yong Yang; Qiang Wang; Jun Wang; Lin Ma; Derek Wyman; Andrew C. Kerr; Xian-Wu Bi; Peng Sun; Xiu-Zheng Zhang; Lu-Lu Hao; Xiao Liu; Chuan-Bing Xu; et al. (Chemical Geology, 2025)

Room temperature natural light promoted DMSO/O2-catalyzed N-acylation reaction of imidazoles/triazoles with cyclopropenones - Guo-Dong Shen; Zhi-Rong Zhao; Kun Bi; Yi Man; Jun-Tong Liu; Xian-Qiang Huang; Xin Lv (Molecular Diversity, 2025)

Is green algae polysaccharide a ‘green path’ to health? - Sammueal Ong Jun Kai; Matthew Myint; Chee Fan Tan; Yi Fan Hong; Meiyappan Lakshmanan; Ying Swan Ho; Thomas T. Wheeler; Xuezhi Bi; Ian Walsh; Sean Chia; Kuin Tian Pang (Algal Research, 2025)

Exploring the symbiotic resilience of boring giant clams and zooxanthellae during heatwave conditions: An investigation into strategic countermeasures - Zhen Zhao; Siqi Bi; Liqiang Zhao; Zohaib Noor; Shuming Guo; Zonglu Wei; Xixi Duan; Yanping Qin; Haitao Ma; Ying Pan; Ziniu Yu; Kotaro Shirai; et al. (Aquaculture, 2025)

Telaprevir attenuates caspase-11-dependent pyroptosis in mouse heart following ischemia/reperfusion via inhibition of MALT1/TRAF6 pathway - Ming-Rui Li; Bi-Feng Yao; Can Tang; Xiu-Ju Luo; Jun Peng (Toxicology and Applied Pharmacology, 2025)

Assessing the methane mitigation potential of biochar and stover incorporation: Insights from the emission dynamics and soil microbiome in maize agroecosystems - Xu Yang; Jun Yuan; Yinghui Bi; Lidan Wang; Junqi Zhang; Chaoqun Wei; Xin Cui; Han Li; Peiyu Luo; Jun Meng; Wenfu Chen (Soil and Tillage Research, 2025)

Rupture mechanism of a liquefied gas storage tank in fire and occurrence prediction of a BLEVE - Weiye Luo; Xingtao Dai; Jingjie Ren; Bing Han; Yan Liu; Jun Hu; Mingshu Bi (Process Safety and Environmental Protection, 2025)

Singlet oxygen-driven non-radical oxidation of phenylurea herbicides in aqueous environment: Reaction behaviors and degradation mechanisms via unactivated PMS systems - Zi-Han Feng; Lin-Hao Xu; Fu-Xiang Tian; Fan Lai; Jing Ye; Yu-Qiong Gao; Dong-Su Bi; Xiao-Jun Hu (Journal of Water Process Engineering, 2025)

Study on combustion characteristics and mechanism of coal gangue under isothermal conditions - Haobo Bi; Jun Chen; Chunlong Jiang; Qizhao Lin (Fuel, 2025)

The flavour substances and key precursor peptides of meaty flavour prepared from Maillard reaction products of Lycium barbarum seed meal - Ya-Fang Shang; Bi-Ming Ding; Zhi-Jing Ni; Kiran Thakur; Jian-Guo Zhang; Zhao-Jun Wei (Food Chemistry, 2025)

Reconstructing Waddington Landscape from Cell Migration and Proliferation - Yourui Han; Bolin Chen; Zhongwen Bi; Jianjun Zhang; Youpeng Hu; Jun Bian; Ruiming Kang; Xuequn Shang (Interdisciplinary Sciences: Computational Life Sciences, 2025)

Deciphering the Therapeutic Mechanisms of Wuzi Yanzong Pill for Asthenozoospermia: A Synergistic Approach Combining Bioinformatics and Molecular Dynamics - Zi-Hao Liu; Shuang-Yang Li; Bi-Jun Li; Fan Zhang; Xiang-Guang Li; Xuan Li; Jie Zheng (Cell Biochemistry and Biophysics, 2025)

Multi-layer grid-scale soil moisture estimation using spatiotemporal deep learning methods with physical constraints - Tuantuan Zhang; Zhongmin Liang; Jianhong Zhou; Quanxi Shao; Ranjan Sarukkalige; Haishen Lü; Jiangjiang Zhang; Chenglin Bi; Jun Wang; Yiming Hu; Binquan Li (Journal of Hydrology, 2025)

Rising attention and shifting themes in green supply chain discourse: Evidence from Weibo (2012–2024) - Shi Wang; Yaxin Hu; Zhan Zhao; Jiacong Cai; Jianxun Yang; Miaomiao Liu; Wen Fang; Zongwei Ma; Jun Bi (Journal of Cleaner Production, 2025)

Improving electrochemical performance of silicon-carbon anode for lithium-ion batteries via one-step etching - Huai-Min Wang; Ying Zhou; Bi-Rong Luo; De-Jun Li; Bo Zhang (Chemical Engineering Journal, 2025)

A matrix for estimating the unfrozen water content of freezing soils - Jun Bi; Guoxu Wang; Wenxuan Mu; Haiyan Wen; Wansheng Pei; Qiyong Zhang; Sheng Yang; Mengyao Mao; Gaochao Lin; Chong Wang (CATENA, 2025)

Bisulfite-free whole-genome mapping of 5-methylcytosine at single-base resolution by NTD-seq - Min Wang; Neng-Bin Xie; Fang-Yin Gang; Shan Zhang; Li Zeng; Tong-Tong Ji; Jun Xiong; Xia Guo; Ying Hao; Yu Liu; Bi-Feng Yuan (Science China Life Sciences, 2025)

Exploring mechanisms of radiation-induced myocardial fibrosis using HMGB1 neutralizing antibody - Gang Wang; Bi-Bo Wu; Sha-Sha Zhao; Jing Zhang; Yu Wang; Yin-Xiang Hu; Jun Wan; Bing Lu; Sheng-Fa Su (Journal of Molecular Histology, 2025)

Probabilistic evaluation of enterprises' fraudulent report in pollutant levels based on machine learning: a case of hazardous waste generation quantity - Wen Fang; Qingyuan Yu; Wenjun Xie; Jianxun Yang; Zongwei Ma; Miaomiao Liu; Jun Bi (Resources, Conservation and Recycling, 2025)

Associations of non-essential metal mixture with biological aging and the mediating role of inflammation in Chinese older adults - Yan Zhang; Yuan Wang; Xuqiu Cheng; Ziwei Tian; Yuantao Zhang; Wenyuan Liu; Xianglong Liu; Bing Hu; Fangbiao Tao; Anna Bi; Jun Wang; Linsheng Yang (Environmental Pollution, 2025)

Ratiometric fluorescent nanoprobes based on lanthanide coordination polymers for visual intelligent detection of phosphate - Yongxin Li; Rongrong Zhou; Fei Xue; Ning Bi; Lina Zhang; Qianyang Li; Kai Shi; Jiang Wu; Lei Jia; Jun Xu (Chemical Engineering Journal, 2025)

Valorisation of spent cultivated meat media for recombinant FGF2 production in Lactococcus lactis - Juliana Rizal; Prashant Mainali; Jun Ping Quek; Lee Ling Tan; Jiawu Bi; Alson Jianchen Chan; Azra Anwar Gaffoor; Lamony Jian Ming Chew; Shigeki Sugii; Say Kong Ng; Dave Siak-Wei Ow; Fong Tian Wong (Systems Microbiology and Biomanufacturing, 2025)

MiR-124 Delivered by Extracellular Vesicles from Mesenchymal Stem Cell Exerts Neuroprotective Effects by Stabilizing the p62-Keap1-Nrf2 Pathway after Spinal Cord Injury in Rats - Chao Fang; Jun Qian; Bi-zhi Tu; Xiang Xia; Chong-yu Jia; Cai-liang Shen (Molecular Neurobiology, 2025)

Balancing textile waste recovery technologies from the environmental, economic, and technological perspectives - Peifan Yao; Fuzheng Shan; Dingyi Li; Han Wang; Lijie Song; Jun Tai; Zhuo Zhang; Qi Tian; Jiefeng Xiao; Zhujie Bi; Jun Zhao; Guangren Qian (Sustainable Production and Consumption, 2025)

Boosting electrochemical activity via manipulating the d-band center of CoNi2Se4/MXene heterostructure for supercapacitor application - Minmin Hu; Lihong Chen; Yu Wang; Jun Dai; Yifan Bi; Yuanming Li; Jian Zhao; Guicun Li; Lei Wang; Alan Meng; Zhenjiang Li (Chemical Engineering Journal, 2025)

U-TWGAN: Underwater image enhancement via wavelet-transformer and sparse multilayer perceptrons generative adversarial network - Jun Zhang; Qilin Bi (Earth Science Informatics, 2025)

ZCCHC3 inhibits PEDV proliferation by degrading nuclear coat proteins via the proteasome pathway - Zuyao Zhang; Shuangyang Wang; Huihui Sun; Jie Li; Jun Wang; Yangfan Li; Haichen Lin; Xuan Wang; Ruimin Bi; Zongyi Bo; Haixiao Shen; Liang Li; et al. (Veterinary Microbiology, 2025)

A better balance: Energy transition and industrial restructuring for a sustainable economy-climate-environment pathway - Jiacong Cai; Jinyang Huang; Jianxun Yang; Miaomiao Liu; Wen Fang; Zongwei Ma; Jun Bi (Journal of Environmental Management, 2025)

A sensitive visual intelligent fluorescence detection platform for tetracycline detection based on silicon quantum dots - Ning Bi; Lixiao Sun; Meihua Hu; Jun Xu; Lina Zhang; Lei Jia (Journal of Environmental Chemical Engineering, 2025)

Melatonin promoted terpene accumulation of blueberries during postharvest partial dehydration - Qin Yang; Hai-Jun Bi; Qi Zhang; Chen Bian; Lu-Lu Zhao; Shu-Qin Huang; Jun Jiang; Hong-Bing Chen; Xue-Ling Gao; Yu Wang (Food Chemistry, 2025)

Chemical profiles and mechanisms insights into Liuwei Dihuang-based formulas in diabetic nephropathy treatment: An integrated transcriptomics with in vitro experiments - Yanxia Liu; Anlei Yuan; Zewen Wang; Shijie Bi; Zhenzhen Xu; Chaoqun Liu; Bin Yu; Jiaye Tian; Liansheng Qiao; Zhaozhou Lin; Jun Jia; Yanling Zhang (Food Bioscience, 2025)

Functional divergence of CAD-like family genes in Saccharum complex under biotic and abiotic stress - Zhu-Qing Wang; Sheng-Ren Sun; Hao-Yu Wang; Zheng-Wang Bi; Hai-Long Chang; Shuo-Hang Zhang; Jun-Lv Chen; Yuan-Xia Qin; Jian-Tao Wu; Wei Zhang; Huan-Ying Xu; San-Ji Gao; et al. (Plant Cell Reports, 2025)

Impacts of fireworks on urban air quality during Spring Festivals of 2022–2024 in Shandong Province, China - Jun Xie; Guixia Wang; Yalian Bi; Chun Ding; Jing Qiao; Lumin Wang; Changwei Wang; Xiaoguo Qiu (Environmental Monitoring and Assessment, 2025)

Comprehensive analysis of transplacental transfer of environmental pollutants detected in paired maternal and cord serums - Ke-Yu Yuan; Yao-Hua Gu; Yi-Hao Pei; Si-Yu Yu; Tian-Zhou Li; Tian Feng; Yu Liu; Jianbo Tian; Xiaoping Miao; Jun Xiong; Min Hu; Bi-Feng Yuan (Journal of Hazardous Materials, 2025)

Accumulation of lipophilic and proteinophilic halogenated organic pollutants (HOPs) in the different types of feathers of laying hens - Xi Chen; Xiao-Jun Luo; Qun-Jie Feng; Yu Liu; Jun-Zhe Dai; Peng-Peng Chen; Pei-Xin Su; Qing-Rong Yang; Yan-Hong Zeng; Bi-Xian Mai (Journal of Hazardous Materials, 2025)

Overcoming the conventional thermodynamic limit of water electrolysis to boost renewable energy storage - Hui Sun; Wen-Tao Bi; Qian He; Li Zhu; Yu-Qing Dong; Fang Li; Zhen-Guo Guo; Jun Ding; Jian-Bo He (Chemical Engineering Journal, 2025)

Experimental study on the mechanical properties and microstructure of purple soil exposed to high temperature conditions - Zhang Qiyong; Lu Zefa; Li Qiang; Bi Jun (Chemical Engineering Journal, 2025)

Unveiling the Spatio-Temporal Patterns and mechanisms of poverty incidence in Southwest China through multi-sourced data and interpretable machine learning - Shenyuan Huang; Yanchuan Shao; Litiao Hu; Jun Bi; Zongwei Ma (Applied Geography, 2025)

Berbamine inhibits Pseudorabies virus in vitro and in vivo - Liang Li; Muze Lv; Yangfan Li; Huihui Sun; Jie Li; Wenyan Li; Xuan Wang; Ruimin Bi; Zuyao Zhang; Zongyi Bo; Haixiao Shen; Jun Wang; et al. (Veterinary Microbiology, 2025)

Identification of the Shuanglongtan tectonic mélange (ca. 1.7–1.5 Ga) in the southwestern Yangtze Block and it’s tectonic implications - Jun-Ping Liu; Zai-Bo Sun; Xiao-Hu He; Jiang-Tai Zhao; Shi-Jun He; Ling-Jing Bi; Wei-Ke Li (Precambrian Research, 2025)

Storage stability evaluation of chicken seasoning by accelerating oil oxidation under different storage conditions - Haoyu Xu; Jun Li; Xiaowei Chen; Yanlan Bi; Xuebing Xu (Food Research International, 2025)

Design of an In Vitro Model for Epithelial-to-Mesenchymal Transition in Gastric Cancer - Yuanhui Zhang; Ling Bi; Quanyao Li; Liqiu Yao; Xiao Wang; Hui Liu; Jun Shi (Biochemical Genetics, 2025)
Epithelial-to-mesenchymal transition (EMT) is a developmental program that plays a vital role in gastric cancer, including aspects of tumor progression, the metastatic process, and resistance to treatment. Here, we have designed an in vitro model that mimics the features of EMT as observed in gastric cancer. The results showed that both migration and invasion were enhanced in gastric cancer cells with Brachyury overexpression. Additionally, the expression of IL-8 increased, while IL-8RA and IL-8RB levels significantly decreased in the in vitro model. Overall, the in vitro model offers an opportunity to study these phenomena relevant to EMT as they may occur in vivo in gastric cancer, as well as potential drug interactions that could interfere with these processes.

Quaternary transgression process controlled by tectonic subsidence over the last 1.35 Ma: New insights from the eastern Bohai Sea - Wei Xiong; Long Huang; Yong Zhang; Zhonglei Wang; Nai Shuang Bi; Jun Pan; Jun Sun; Lelong He; Feifei Wang; Xi Mei (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Effect of biochar on anaerobic co-digestion performance of cellulosic ethanol refinery waste liquor with swine manure - Haoran Li; Sunqiang Xu; Yingyan Liang; Can Fu; Yongxin Pang; Zhantian Tang; Guican Bi; Jun Xie (Journal of Water Process Engineering, 2025)

Nobiletin, an activator of the pyruvate kinase isozyme M1/M2 protein, upregulated the glycolytic signalling pathway and alleviated depressive-like behaviour caused by artificial light exposure at night in zebrafish - Meng-ling Zhang; Xiao-peng Li; Li-fang Gao; Jian Liu; Zi-jun Bi; Yu-han Miao; Yang Shan; Huan-ling Yu (Food Chemistry, 2025)

Statistical Post-Processing for Precipitation Forecast Through Deep Learning Coupling Large-Scale and Local-Scale Spatiotemporal Information - Tuantuan Zhang; Zhongmin Liang; Chenglin Bi; Jun Wang; Yiming Hu; Binquan Li (Water Resources Management, 2025)

Acid-etched halloysite and Co-Ni-B composites for high-performance supercapacitor application - Fan Yang; Xue-Jing Ma; Jun-Hu Liu; Bi Chen; Kang Yang; Xin-Yu Liu; Wei-Bin Zhang (Applied Clay Science, 2025)

Biomagnification of polybrominated diphenyl ethers and alternative halogenated flame retardants through food chains of yellowfin tuna (Thunnus albacares) and their prey from the South China Sea and the associated potential health risk - Run-Xia Sun; Chang-Gui Pan; Feng-Jiao Peng; Zhong-Biao Chen; Yue Sun; Jiang-Tao Fan; Jun Zhang; Bi-Xian Mai (Science of The Total Environment, 2024)

Cascaded reservoirs promote phosphorus bioavailability of surface sediments in the Upper Mekong River - Zhengjian Yang; QiFeng Min; Xiaojuan Guo; Congfeng Wang; Bi'’e Yan; Xiaoling Li; Defu Liu; Jun Ma; Andreas Lorke (Science of The Total Environment, 2024)

Advances and future directions of environmental risk research: A bibliometric review - Jinghua Geng; Wen Fang; Miaomiao Liu; Jianxun Yang; Zongwei Ma; Jun Bi (Science of The Total Environment, 2024)

Predicting the volumetric heat capacity of freezing soils using the soil freezing characteristic curve - Jun Bi; Yuxuan Pan; Sheng Yang; Renwei Li; Zhijian Wu (Journal of Hydrology, 2024)

Unveiling the critical roles of nascent MnO2 in accelerating permanganate carbocatalysis - Jun Wang; Simeng Bi; Li Wei; Yi Shen; Fanpeng Meng; Yang Zhang; Xiaoyao Tan (Journal of Hazardous Materials, 2024)

A new method to estimate the soil freezing characteristic curve - Jun Bi; Chaozheng Shen; Guoxu Wang; Zhijian Wu; Sheng Yang; Jianguo Lu; Gaochao Lin (Cold Regions Science and Technology, 2024)

Perioperative complications of middle cerebral artery occlusion in rats alleviated by human umbilical cord mesenchymal stem cells - Liang Liu; Yating Luo; Tao Xu; Qisheng Tang; Jialian Yi; Linping Wang; Shixiang Luo; Zhaohong Bi; Jianlei Liu; Jun Lu; Weiwei Bi; Changguo Peng; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Effects of alligator weed invasion on wetlands in protected areas: A case study of Lishui Jiulong National Wetland Park - Xiang-Hua Fang; Xuan-Ming Chen; Ri-Lin Liu; Si-Hai Zhang; Jun-Qin Gao; Bi-Cheng Dong; Fei-Hai Yu (Science of The Total Environment, 2024)

Evaluation and comparison of iohexol elimination by UV/peroxymonosulfate and UV/persulfate processes: Radical roles, influence factors and iodinated trihalomethanes formation - Chen-Cheng Mo; Fu-Xiang Tian; Bin Xu; Fan Lai; Yu-Qiong Gao; Yan Ma; Zi-Han Feng; Zi-Jian Yao; Dong-Su Bi; Xiao-Jun Hu (Journal of Water Process Engineering, 2024)

Tuning local charge polarization of covalent organic frameworks for enhanced photocatalytic uranium (VI) reduction - Xiao-Xing Wang; Cheng-Rong Zhang; Rui-Xiang Bi; Zhi-Hai Peng; Hao-Xuan He; Rui Zhang; An-Min Song; Jia-Xin Qi; Xiao-Juan Chen; Xin Liu; Yuan-Jun Cai; Ru-Ping Liang; et al. (Chemical Engineering Journal, 2024)

Drugs targeting TGF-β/Notch interaction attenuate hypertrophic scar formation by optic atrophy 1-mediated mitochondrial fusion - Da Huo; Xin-yu Bi; Jun-ling Zeng; Da-mao Dai; Xiang-lin Dong (Molecular and Cellular Biochemistry, 2024)

Relevance and mechanism of STAT3/miR-221-3p/Fascin-1 axis in EGFR TKI resistance of triple-negative breast cancer - Lu-Lu Jin; Hua-Jun Lu; Jun-Kang Shao; Yan Wang; Shi-Ping Lu; Bi-Fei Huang; Gui-Nv Hu; Hong-Chuan Jin; Chao-Qun Wang (Molecular and Cellular Biochemistry, 2024)

Cloning and Functional Characterization of LlAS1 in Lilium lancifolium - Yuxiao Qu; Panpan Yang; Mengmeng Bi; Leifeng Xu; Jun Ming (Journal of Plant Growth Regulation, 2024)

The effects of top-down political inspection on bottom-up public complaints in China - Jinchi Dong; Miaomiao Liu; Wei Zhang; Hongqiang Jiang; Jinnan Wang; Bing Zhang; Ye Shu; Li Sun; Jun Bi (Journal of Cleaner Production, 2024)

The LINGO-1-deficient neural stem cell-derived neural tissueoid showed enhanced retention and neuronal relay in the transected spinal cord - Ge Li; Li-Jun Huang; Bao Zhang; Shu Liu; Jing-Hua Liang; Ying Ding; Xiang Zeng; Bi-Qin Lai; Yuan-Huan Ma; Ya-Qiong Wang; Rui Wang; Hong-Bo Zhang; et al. (Chemical Engineering Journal, 2024)

Nontarget analysis and characterization of p-phenylenediamine-quinones and -phenols in tire rubbers by LC-HRMS and chemical species-specific algorithm - Caiming Tang; Yizhe Zhu; Ruifen Zheng; Ling Liu; Yan-Hong Zeng; Xiao-Jun Luo; Bi-Xian Mai (Analytica Chimica Acta, 2024)

Smartphone-assisted mobile fluorescence sensor for self-calibrated detection of anthrax biomarker, Cu2+, and cysteine in food analysis - Sheng Wang; Jun Xu; Fengzhi Yue; Lina Zhang; Ning Bi; Jian Gou; Yongxin Li; Yuanyuan Huang; Tongqian Zhao; Lei Jia (Food Chemistry, 2024)

Supercapacitor-isolated water electrolysis for renewable energy storage - Qian He; Hui Sun; Wen-Tao Bi; Xin-Yuan Wang; Bing Li; Fang Li; Zhen-Guo Guo; Jun Ding; Jian-Bo He (Chemical Engineering Journal, 2024)

Three new lanostane triterpenoids and two new amides from Alternaria sp. with NLRP3 inflammasome inhibitory activity - De-Wen Bi; Jian- Feng; Wen-Hui Pang; Peng-Yun Yang; Yao-Jun Xu; Muhammad Aurang Zeb; Meng-Ru Wang; Xing-Jie Zhang; Xiao-Li Li; Rui-Han Zhang; Wei-Guang Wang; Wei-Lie Xiao (Natural Product Research, 2024)

H3K4 Trimethylation Mediate Hyperhomocysteinemia Induced Neurodegeneration via Suppressing Histone Acetylation by ANP32A - Gao-shang Chai; Juan Gong; Yu-ming Mao; Jia-jun Wu; Shu-guang Bi; Fangzhou Wang; Yu-qi Zhang; Meng-ting Shen; Zhuo-ya Lei; Yun-juan Nie; Haitao Yu (Molecular Neurobiology, 2024)

Genetic and recombination heterogeneity of canine bufaviruses detected in diarrheal dogs in China - Jun Ji; Hao Cui; Zhibin Zhang; Qiang Liu; Xin Xu; Kejing Zuo; Yingzuo Bi; Lunguang Yao (The Veterinary Journal, 2024)

First outbreak of trypanosomiasis in farmed blood parrot cichlids (Vieja melanura♀ × Amphilophus citrinellus♂) from southern China - Jun-Yu (俊余) Zhou (周); Liwen (力文) Xu (徐); Ying-Xin (潆心) Bi (毕); Jinyong (晋勇) Zhang (章); Geoff Hide; De-Hua (德华) Lai (赖); Zhao-Rong (照荣) Lun (伦) (Aquaculture, 2024)

Occurrence, distribution, and ecological risk assessment of pharmaceuticals and personal care products in the surface water of Lipu River, China - Yanan Zhang; Guibin Huang; Qin Zhang; Xiaoqian Bi; Hang Chu; Zixuan Liu; Jun Luo; Shaoyuan Bai; Shengpeng Mo; Hui Wang; Mingming Fu (Environmental Research, 2024)

Tetrabromobisphenol-A/S and their derivatives in surface particulates from workshop floors of three representative e-waste recycling sites in China - Hui Yang; Xiao-Jun Luo; Jia-Zhuo He; Yan-Hong Zeng; Bi-Xian Mai; Li-Zhong Wang; Xiang Bi (Environmental Research, 2024)

Laboratory study on the frost-proof performance of a molecular vibration infrared Nano-thermoprobe (MVINT) embankment in seasonally frozen ground regions - Zhijian Wu; Guoxu Wang; Jun Bi; Wang Cao; Chengxin Chu; Yu Lu; Tian Sun; Bowen Tai (Cold Regions Science and Technology, 2024)

Effectiveness of a novel compound microbial agent for water quality and the gut microbiota of Micropterus salmoides - Qian Li; Li-Hui Sun; Bi-Cheng Yang; Jian-Hu Jiang; Jian-Ming Chen; Gang Zheng; Ling-Mei Gao; Jun Peng; Jian-Lin Guo (Frontiers in Marine Science, 2024)
The cultivation of largemouth bass ( Micropterus salmoides ), a species of significant economic value in aquaculture, has experienced notable growth recently. However, the deterioration of water quality seriously affects the metabolic responses of M. salmoides . While compound microbial agent (CMA) is widely utilized for ecological rehabilitation and water filtration, its application in M. salmoides has not been reported. Here, based on physio-biochemical tests and 16S rRNA sequencing, we investigated the effects of CMA (yeast, Bacillus subtilis , and lactic acid bacteria) on the water quality within the recirculating aquaculture system, along with physiological indices and gut microbiota of M. salmoides . Compared to the control and single microbial agent (yeast), CMA treatment improved the water quality by improving the dissolved oxygen and delaying the increase of pH, total nitrogen, total phosphorus, ammonia nitrogen, and nitrite. The 16s rRNA gene sequencing revealed that the water treated with CMA exhibited elevated levels of chao1, Shannon, Pd, and a larger population of dominant bacterial. Besides, higher values of ACE, chao1, Shannon, and OTU level, and lower Simpson index were found in CMA treated M. salmoides samples, suggesting that CMA treatment enhanced the species richness and diversity of gut microbiota of M. salmoides . Furthermore, CMA treatment hindered the generation and proliferation of harmful bacteria, such as the Mycoplasma mobile 163K species and the Erysipelotrichaceae family, which was associated with enhanced antioxidant enzymatic activity and decreased MDA level in both the serum and liver. These findings shed light on the essential roles of CMA in M. salmoides culturing and introduce an innovative approach to enhance the aquatic environment.

Lily (Lilium spp.) LhERF4 negatively affects anthocyanin biosynthesis by suppressing LhMYBSPLATTER transcription - Yu-wei Cao; Meng Song; Meng-meng Bi; Pan-pan Yang; Guo-ren He; Jing Wang; Yue Yang; Lei-feng Xu; Jun Ming (Plant Science, 2024)

CeMgOx-promoted Ni/boron nitride ultra-long stability bi-reforming for methanol-friendly syngas (H2/CO≈2): CO2/H2O activation and coke elimination mechanism - Zhige Zhang; Guican Bi; Shenglong Zhang; Tao Tan; Jun Xie (Fuel, 2024)

A sensitive fluorometric-colorimetric dual-mode intelligent sensing platform for the detection of formaldehyde - Xiangzhen Chen; Jun Xu; Lina Zhang; Ning Bi; Jian Gou; Yongxin Li; Tongqian Zhao; Lei Jia (Food Chemistry, 2024)

Overview of the recent advances in porcine epidemic diarrhea vaccines - Miao-Zhan Wei; Lan Chen; Rong Zhang; Ze Chen; Yan-Juan Shen; Bi-Jun Zhou; Kai-Gong Wang; Chun-Lan Shan; Er-Peng Zhu; Zhen-Tao Cheng (The Veterinary Journal, 2024)

Environmental arsenic pollution induced liver oxidative stress injury by regulating miR-155 through inhibition of AUF1 - Ying Lv; Hongling Wang; Dan Zheng; Mingyang Shi; Dingnian Bi; Qian Hu; Haiyan Zhi; Didong Lou; Jun Li; Shaofeng Wei; Yong Hu (Science of The Total Environment, 2024)

Efficient trimethoprim removal via cooperation of radical and non-radical pathways in UV/peroxymonosulfate: Kinetics, mechanisms and disinfection by-products-associated risks - Chen-Cheng Mo; Fu-Xiang Tian; Bin Xu; Juan Wang; Yu-Qiong Gao; Dong-Su Bi; Bo Wang; Xing-Yan Mu; Xiao-Jun Hu (Journal of Environmental Chemical Engineering, 2024)

A renal-targeted gene delivery system derived from spermidine for arginase-2 silencing and synergistic attenuation of drug-induced acute kidney injury - Xu-Rui Gu; Kun Liu; Yi-Xuan Deng; Bi-Xiao Xiang; Ling-Yun Zhou; Wen-Jun Yin; Jia-Xin Huang; Ying-Cai Meng; Dian-Ke Li; Rui-Man Que; Zhi-Yao Tang; Guang-Liang Zhou; et al. (Chemical Engineering Journal, 2024)

Clay minerals modified nickel boride for electrochemical supercapacitor electrode application - Fan Yang; Xue-Jing Ma; Jing-Lei Yang; Jun-Hu Liu; Bi Chen; Xin-Yu Liu; Kang Yang; Wei-Bin Zhang (Applied Clay Science, 2024)

Economic risks hidden in local water pollution and global markets: A retrospective analysis (1995–2010) and future perspectives on sustainable development goal 6 - Jianxun Yang; Jinling Li; Michelle T.H. van Vliet; Edward R. Jones; Zhongwei Huang; Miaomiao Liu; Jun Bi (Water Research, 2024)

Biochar application alters soil metabolites and nitrogen cycle-related microorganisms in a soybean continuous cropping system - Xin Cui; Jun Yuan; Xu Yang; Chaoqun Wei; Yinghui Bi; Qiang Sun; Jun Meng; Xiaori Han (Science of The Total Environment, 2024)

Insights into the occurrence, spatial distribution, and ecological implications of organophosphate triesters in surface sediments from polluted urban rivers across China - Yin-E Liu; Xiao-Jun Luo; Chen-Chen Huang; Qihong Lu; Shanquan Wang; Bi-Xian Mai (Science of The Total Environment, 2024)

Enhancement of ester biosynthesis in blueberry wines through co-fermentation via cell–cell contact between Torulaspora delbrueckii and Saccharomyces cerevisiae - Yu Wang; Yu Fu; Qi Zhang; Yue Zhu; Qin Yang; Chen Bian; Lu-Lu Zhao; Qi Chen; Hai-Jun Bi; Xiao-Hui Yang; Xue-Ling Gao (Food Research International, 2024)

Endothelial extracellular vesicles induce acute lung injury via follistatin-like protein 1 - Hao-Xiang Yuan; Ya-Ting Chen; Yu-Quan Li; Yan-Sheng Wang; Zhi-Jun Ou; Yan Li; Jian-Jun Gao; Meng-Jie Deng; Yuan-Kai Song; Li Fu; Hong-Bo Ci; Feng-Jun Chang; et al. (Science China Life Sciences, 2024)

City-level resilience to extreme weather shocks revealed by satellite nighttime lights in China - Litiao Hu; Jing Meng; Chaoying Xiong; Wen Fang; Jianxun Yang; Miaomiao Liu; Jun Bi; Zongwei Ma (Sustainable Cities and Society, 2024)

Effect of corn stalks on coal catalytic hydrogasification in a pressurized fluidized bed for manufacturing CH4 - Shuai Yan; Jun Feng; Zihong Xia; Yingying Huang; Fengshuang Han; Xuan Qu; Jicheng Bi (Fuel, 2024)

A comprehensive assessment of external exposure to persistent halogenated organic pollutants for residents in an e-waste recycling site, South China - Yin-Zhi Lv; Xiao-Jun Luo; Xue-Meng Qi; Ke-Lan Guan; Yan-Hong Zeng; Bi-Xian Mai (Environmental Pollution, 2024)

Assessment and enhancement of soil freezing characteristic curve estimation models - Jun Bi; Laifu Li; Zhenyu Liu; Zhijian Wu; Guoxu Wang (Cold Regions Science and Technology, 2024)

High-density lipoprotein regulates angiogenesis by affecting autophagy via miRNA-181a-5p - Bi-Ang Kang; Hua-Ming Li; Ya-Ting Chen; Meng-Jie Deng; Yan Li; Yue-Ming Peng; Jian-Jun Gao; Zhi-Wei Mo; Jia-Guo Zhou; Zhi-Jun Ou; Jing-Song Ou (Science China Life Sciences, 2024)

The role of corneal endothelium in macular corneal dystrophy development and recurrence - Bi-Ning Zhang; Benxiang Qi; Chunxiao Dong; Bin Zhang; Jun Cheng; Xin Wang; Suxia Li; Xiaoyun Zhuang; Shijiu Chen; Haoyun Duan; Dewei Li; Sujie Zhu; et al. (Science China Life Sciences, 2024)

Machine learning algorithms realized soil stoichiometry prediction and its driver identification in intensive agroecosystems across a north-south transect of eastern China - Xintong Xu; Chao Xiao; Yubing Dong; Liping Zhan; Ruiyu Bi; Mengxin Song; Jun Pan; Zhengqin Xiong (Science of The Total Environment, 2024)

Comprehensive evaluation of air pollution emission permit allocation: Effectiveness, efficiency, and equity in China's environmental management framework - Jia Zhou; Jinnan Wang; Jun Bi; Qi Zhou (Journal of Cleaner Production, 2024)

Dimensionally-controlled interlayer spaces of covalent organic frameworks for the oxygen evolution reaction - Minghao Liu; Yubin Fu; Shuai Bi; Shuai Yang; Xiubei Yang; Xuewen Li; George Zheng Chen; Jun He; Qing Xu; Gaofeng Zeng (Chemical Engineering Journal, 2024)

Bioaccumulation, tissue distributions, and maternal transfer of perfluoroalkyl carboxylates (PFCAs) in laying hens - Qun-Jie Feng; Xiao-Jun Luo; Mei-Xia Ye; Ke-Qi Hu; Yan-Hong Zeng; Bi-Xian Mai (Science of The Total Environment, 2023)

Estimation of daily NO2 with explainable machine learning model in China, 2007–2020 - Yanchuan Shao; Wei Zhao; Riyang Liu; Jianxun Yang; Miaomiao Liu; Wen Fang; Litiao Hu; Matthew Adams; Jun Bi; Zongwei Ma (Atmospheric Environment, 2023)

Preparation and potential applications of alginate oligosaccharides - Decheng Bi; Xu Yang; Jun Lu; Xu Xu (Critical Reviews in Food Science and Nutrition, 2023)

Aroma enhancement of blueberry wine by postharvest partial dehydration of blueberries - Yu Wang; Qi Zhang; Meng-Yao Cui; Yu Fu; Xiao-Han Wang; Qin Yang; Yue Zhu; Xiao-Hui Yang; Hai-Jun Bi; Xue-Ling Gao (Food Chemistry, 2023)

A multifunctional surgical suture with electroactivity assisted by oligochitosan/gelatin-tannic acid for promoting skin wound healing and controlling scar proliferation - Hui Han; Liqin Tang; Yan Li; Yong Li; Ming Bi; Jun Wang; Fujun Wang; Lu Wang; Jifu Mao (Carbohydrate Polymers, 2023)

Organophosphate diesters (DAPs) and hydroxylated organophosphate flame retardants (HO-OPFRs) as biomarkers of OPFR contamination in a typical freshwater food chain - Yin-E Liu; Xiao-Jun Luo; Hong-Chang Ding; Lin Qi; Bin Tang; Bi-Xian Mai; Giulia Poma; Adrian Covaci (Chemosphere, 2023)

Understanding individuals’ choice-making mechanism in trip chains of shared autonomous vehicles - Chengdong Zhou; Xiaomei Zhao; Dongfan Xie; Jun Bi (Travel Behaviour and Society, 2023)

The heterogeneous effects of Chinese industrial parks on environmental pollution - Jiong Lu; Qi Zhou; Weixiao Qi; Shen Qu; Jun Bi (Science of The Total Environment, 2023)

Immunogenicity and safety of an Escherichia coli-produced human papillomavirus (types 6/11/16/18/31/33/45/52/58) L1 virus-like-particle vaccine: a phase 2 double-blind, randomized, controlled trial - Yue-Mei Hu; Zhao-Feng Bi; Ya Zheng; Li Zhang; Feng-Zhu Zheng; Kai Chu; Ya-Fei Li; Qi Chen; Jia-Li Quan; Xiao-Wen Hu; Xing-Cheng Huang; Kong-Xin Zhu; et al. (Science Bulletin, 2023)

High potential of coupling the source-separation and incineration promotion to reduce costs based on city-level cost-benefit analysis of municipal solid waste management strategies in China - Wen Fang; Yimeng Ding; Jinghua Geng; Zheng Liu; Yujie Huang; Jianxun Yang; Zongwei Ma; Jianguo Liu; Jun Bi; Miaomiao Liu; Zhan Qu (Resources, Conservation and Recycling, 2023)

Corrigendum to ‟Joint optimization of infrastructure deployment and fleet operations for an electric car sharing system by considering multi-type vehicles” [J. Clean. Prod. 414 (2023) 137681] - Qiuyue Sai; Jun Bi; Xiaomei Zhao; Wei Guan; Chaoru Lu (Journal of Cleaner Production, 2023)

Influences of a variable nozzle turbocharger on the combustion and emissions of a light-duty diesel engine at different altitudes - Jun Wang; Lizhong Shen; Yuhua Bi; Jilin Lei (Fuel, 2023)

A wearable gloved sensor based on fluorescent Ag nanoparticles and europium complexes for visualized assessment of tetracycline in food samples - Jun Xu; Junxi Wang; Yongxin Li; Lina Zhang; Ning Bi; Jian Gou; Tongqian Zhao; Lei Jia (Food Chemistry, 2023)

p-Nrf2/HO-1 Pathway Involved in Methamphetamine-induced Executive Dysfunction through Endoplasmic Reticulum Stress and Apoptosis in the Dorsal Striatum - Tao Wei; Jun-Da Li; Yu-Jing Wang; Wei Zhao; Fan Duan; Yan Wang; Ling-Ling Xia; Zhao-Bin Jiang; Xun Song; Yu-Qiong Zhu; Wen-Yi Shao; Ze Wang; et al. (Neurotoxicity Research, 2023)

Development of microfluidic chip flowmeter-based constant pressure system for analysing the hydrogen adsorption performance of non-evaporable getters - Wenyu Lin; Wei Wei; Jun Wu; Qing Cao; Hailin Bi; Jun Zhang; Zhengwei Mei; Jian Jin; Xudi Wang (Analytica Chimica Acta, 2023)

Megacity's pathway toward sustainable food waste management and its environmental performance in a developing country: Evidence from Shanghai, China - Jiefeng Xiao; Tao Tao; Yuqing Shi; Jun Zhao; Bingsi Wu; Jun Tai; Mengqi Xu; Xing Zhang; Yuru Peng; Zhujie Bi; Di Feng; Guangren Qian (Science of The Total Environment, 2023)

Regeneration of high-performance materials for electrochemical energy storage from assorted solid waste: A review - Jia-feng Zhang; De-zhao Peng; Xiang-gang Gao; Jing-tian Zou; Long Ye; Guan-jun Ji; Bi Luo; Gui-hui Yu; Peng-fei Li; Xiao-wei Wang; Zao-wen Zhao; Bao Zhang; et al. (Journal of Cleaner Production, 2023)

Joint optimization of infrastructure deployment and fleet operations for an electric carsharing system by considering multi-type vehicles - Qiuyue Sai; Jun Bi; Xiaomei Zhao; Wei Guan; Chaoru Lu (Journal of Cleaner Production, 2023)

Bi-reforming of model biogas to syngas over Ru nano-catalysts supported on Mg-Al oxide derived from layered double hydroxides - Jiawei Zhong; Bing Han; Zhige Zhang; Guican Bi; Jun Xie (Fuel, 2023)

Screening and functional analysis of three Spiroplasma eriocheiris glycosylated protein interactions with Macrobrachium nipponense C-type lectins - Keran Bi; Jie Du; Jun Chen; Huicong Wang; Kun Zhang; Yuheng Wang; Libo Hou; Qingguo Meng (Fish & Shellfish Immunology, 2023)

Analysis of seismic damage of a highway bridge during the 2021 Ms 7.4 earthquake in Maduo County, China - Wanpeng Ding; Zhijian Wu; Beilei Zhan; Jian Liu; Jun Bi (Natural Hazards, 2023)

The impacts of spatio-temporal variation of natural and agricultural influences on the environmental water quality in a fluvial-lacustrine watershed in China - Yu Feng; Bing-Hui Zheng; Hai-Feng Jia; Bing-Bing Song; Yang Liu; Jun-Ping Bi (Environmental Science and Pollution Research, 2023)

The potential risks posed by micro-nanoplastics to the safety of disinfected drinking water - Shuan Liu; Haojie Ding; Yunqian Song; Yinghao Xue; Mohan Bi; Meirou Wu; Chun Zhao; Min Wang; Jun Shi; Huiping Deng (Journal of Hazardous Materials, 2023)

Characteristics of changes in volatile organic compounds and microbial communities during the storage of pickles - Xi-han Sun; Xin Qi; Yu-di Han; Zhi-jun Guo; Cheng-bi Cui; Chang-qing Lin (Food Chemistry, 2023)

Indoor PM2.5, home environmental factors and lifestyles are related to sick building syndrome among residents in Nanjing, China - Zhijuan Shao; Jun Bi; Jie Yang; Zongwei Ma (Building and Environment, 2023)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

Dosage effect of anthocyanin biosynthesis in purple-grained wheat (Triticum aestivum L.) - Chan Bi; Chaoxiong Wei; Shuai Tian; Jinghui Li; Yufeng Zhang; Jun Ma; Mingshan You (Euphytica, 2023)

Elevated Interleukin-37 Associated with Dengue Viral Load in Patients with Dengue Fever - Jun-Ai Zhang; Jia-Jun Wang; Wen-Ting Zhang; Li Zhang; Bi-Ying Zheng; Gan-Bin Liu; Jing Liang; Yuan-Bin Lu; Xian-Jin Wu; Shu-Ying Yao; Guo-Ying Chen; Yun-Qi Xie; et al. (Current Microbiology, 2023)
Dengue remains a public health issue worldwide. Similar to chronic infectious diseases, stimulation of cytokine production is not enough to drive immune effector cells for effective virus clearance. One possible mechanism is the virus induces a large number of negative stimulatory cytokines inhibiting immune response. Interleukin 37 (IL-37) plays a crucial regulatory role in infection and immunity, inhibits innate and adaptive immunity as an anti-inflammatory cytokine by inhibiting proinflammatory mediators and pathways. To date, there are few studies reporting correlations between dengue fever (DF) and IL-37. In this study we found that the serum IL-37b and IL-37b-producing monocytes in patients were significantly increased in DF patients. A majority of the IL-37b produced by DF patients was produced by monocytes, not lymphocytes. Increased levels of IL-6, IL-10, and IFN-α were also found in DF patients. However, we failed to detect IL-1β, IL-17A and TNF-α in plasma, because of off-target. In our study, there was no relation between IL-6, IL-10, and IFN-α expressions and IL-37b in serum ( P > 0.05). The IL-37b-producing monocytes were negatively correlated with the level of IFN-α in serum and platelet count, and positively correlated with lymphocytes percentage ( P < 0.05, respectively). Additionally, serum DENV nonstructural protein 1 levels were positively correlated with monocytes percentages ( P < 0.05). Our data represents findings for IL-37b expression and its potential mechanisms in DF patients’ immune response.

Tracking the life-cycle greenhouse gas emissions of municipal solid waste incineration power plant: A case study in Shanghai - Xiaoqu Han; Hongzhang Chang; Chuan Wang; Jun Tai; Sotirios Karellas; Junjie Yan; Lijie Song; Zhujie Bi (Journal of Cleaner Production, 2023)

Recycling and reuse performance of cobalt catalyst for coal hydrogasification - Jun Feng; Shuai Yan; Rong Zhang; Sumin Gu; Xuan Qu; Jicheng Bi (Fuel, 2023)

A novel intelligently integrated MOF-based ratio fluorescence sensor for ultra-sensitive monitoring of TC in water and food samples - Xiangzhen Chen; Jun Xu; Yongxin Li; Lina Zhang; Ning Bi; Jian Gou; Taofeng Zhu; Lei Jia (Food Chemistry, 2023)

Fouling characteristic of reverse osmosis membrane for reclaimed water treatment operating under cold winter condition - Zi-Hao Li; Guo-Wei Ni; Jin-Long Wang; Lin Zhou; Qiang Yang; Pei-Zhuo Li; Ai-Li Gao; Tong Yu; Li-Hua Cheng; Xue-Jun Bi (Desalination, 2023)

Iron-fortified Anaerobic Co-digestion Performance of Kitchen Waste and Pennisetum Hybrid - Defang Wo; Guican Bi; Lianhua Li; Xiaoying Kong; Enchen Jiang; Jun Xie (BioEnergy Research, 2023)

Occurrence, spatial distribution, and risk assessment of short- and medium-chain chlorinated paraffins in sediment from black-odorous rivers across China - Ke-Lan Guan; Xiao-Jun Luo; Qi-Hong Lu; Chen-Chen Huang; Xue-Meng Qi; Yan-Hong Zeng; Bi-Xian Mai; Shan-Quan Wang (Chemosphere, 2023)

Inactivation of Escherichia coli and Vibrio parahaemolyticus on polypropylene plastic container surfaces by non-thermal dielectric barrier discharge plasma - Ji Yoon Kim; Min Gyu Song; Eun Bi Jeon; Eun Ha Choi; Jun Sup Lim; Shin Young Park (Journal of Food Engineering, 2023)

Towards next generation design of sustainable, durable, multi-hazard resistant, resilient, and smart civil engineering structures - Hong Hao; Kaiming Bi; Wensu Chen; Thong M. Pham; Jun Li (Engineering Structures, 2023)

A flexible zinc ion hybrid capacitor integrated system with layers-dependent V2CTx MXene - Sairao Zhao; Xiao Luo; Yongfa Cheng; Zhixiang Shi; Tao Huang; Shanghua Yang; Haojian Zheng; Yun Bi; Jun Zhang; Qiuyue Shi; Minglei Cao; Chuankun Zhang; et al. (Chemical Engineering Journal, 2023)

Optimizing embankment structures in a snowy permafrost region of the pan-Arctic based on a coupled numerical model - Sheng Yang; Mingyi Zhang; Jun Bi; Wansheng Pei; Ruiqiang Bai (Transportation Geotechnics, 2023)

Impacts of springtime biomass burning in Southeast Asia on atmospheric carbonaceous components over the Beibu Gulf in China: Insights from aircraft observations - Xiaoyang Yang; Dongsheng Ji; Jiawei Li; Jun He; Chongshui Gong; Xiaojuan Xu; Zhe Wang; Yu Liu; Fang Bi; Zhongzhi Zhang; Yunbo Chen (Science of The Total Environment, 2023)

Fetal exposure to organic contaminants revealed by infant hair: A preliminary study in south China - Feng-Shan Cai; Bin Tang; Jing Zheng; Xiao Yan; Wei-Keng Luo; Mian He; Xiao-Jun Luo; Ming-Zhong Ren; Yun-Jiang Yu; Bi-Xian Mai (Environmental Pollution, 2023)

Construction of 3D Ni2+-Al3+-LDH/γ-Fe2O3-Cd2+-Ni2+-Fe3+-LDH structures and multistage recycling treatment of dye and fluoride-containing wastewater - Rui Dang; Xiang-Rong Ma; Yun-Peng Zhao; Menjiao Ren; Wei Guo; Yu-Hong Kang; Yong Gao; Shiqing Bi; Wenwen Gao; Hua-Rui Hao; Rui Bai; Yu-Fei Wang; et al. (Chemical Engineering Journal, 2023)

DsRNAs spray enhanced the virulence of entomopathogenic fungi Beauveria bassiana in aphid control - Jun Zhang; Chao Ye; Zi-Guo Wang; Bi-Yue Ding; Guy Smagghe; Yongjun Zhang; Jinzhi Niu; Jin-Jun Wang (Journal of Pest Science, 2023)

A new insight into the emission source of DDT in indoor environment from rural area of South China and comprehensive human health exposure assessment - Yin-Zhi Lv; Xiao-Jun Luo; Qi-Qi Li; Yan Yang; Yan-Hong Zeng; Bi-Xian Mai (Environmental Science and Pollution Research, 2022)

Relation of Carotid Plaque Features Detected with Ultrasonography-Based Radiomics to Clinical Symptoms - Zhe Huang; Xue-Qing Cheng; Hong-Yun Liu; Xiao-Jun Bi; Ya-Ni Liu; Wen-Zhi Lv; Li Xiong; You-Bin Deng (Translational Stroke Research, 2022)

Hydrothermal carbonization of alfalfa: role of processing variables on hydrochar properties - Jun Zhou; Mingjie Yu; Jianhua Qu; Modupe Sarah Akindolie; Fuxuan Bi; Yang Liu; Zhao Jiang; Lei Wang; Bo Zhang; Ying Zhang (Environmental Science and Pollution Research, 2022)

Highly stable and efficient calcined γ-Al2O3 catalysts loaded with MnOx-CeOx for the ozonation of oxytetracycline - Xinpeng Shu; Huaqi Bi; Jun Wang; Jiaxin Yang; Jue Wang; Guangqing Liu; Bensheng Su (Environmental Science and Pollution Research, 2022)

Vacuum Foam Drying Method Improved the Thermal Stability and Long-Term Shelf Life of a Live Attenuated Newcastle Disease Virus Vaccine - Fang Lyu; Yan-hong Zhao; Yu Lu; Xiao-xin Zuo; Bi-hua Deng; Min-qian Zeng; Jun-ning Wang; Ademola Olaniran; Jibo Hou; Thandeka Khoza (AAPS PharmSciTech, 2022)

Long‐term series variation in fishery biology of Dosidicus gigas off Peru: Response to climate variability from 2008 to 2020 - Ya Ting Dan; Bi Lin Liu; Xin Jun Chen; Wei Guo Qian (Fisheries Oceanography, 2022)
As a cephalopod with a short life cycle, the Dosidicus gigas (jumbo flying squid) is extremely sensitive to climate variability and marine environment changes in terms of individual growth and resource changes. Based on 7514 D. gigas samples collected off Peru from 2008 to 2020, the fishery biological characteristics such as size, sexual maturity, and size‐at‐maturity were analyzed to explore the impacts of climate variability on individual growth. The results showed that there were significant differences in the relationship between mantle length and body weight and in the composition of sexual maturity between male and female individuals in different years ( P D. gigas and slowed down their sexual maturity, producing D. gigas groups in medium and large sizes; El Niño events inhibited the individual growth of D. gigas and accelerated their sexual maturity, producing D. gigas groups in a smaller size. From 2008 to 2020, the mantle length of the small‐size group decreased by 46 mm, while that of the medium‐size group increased by 28 mm. Size‐at‐maturity of female D. gigas decreased by 201.2 mm and that of male D. gigas decreased by 143 mm. The study concluded that the changes in the marine environment caused by climate variability from 2008 to 2020 have had a significant impact on the population structure, growth, and development of the D. gigas off Peru.

Loss of Myomixer Results in Defective Myoblast Fusion, Impaired Muscle Growth, and Severe Myopathy in Zebrafish - Ping Wu; Pengzheng Yong; Zhanxiong Zhang; Rui Xu; Renjie Shang; Jun Shi; Jianshe Zhang; Pengpeng Bi; Elizabeth Chen; Shaojun Du (Marine Biotechnology, 2022)

Modeling impacts of mining activity-induced landscape change on local climate - Hongru Bi; Wei Chen; Jun Li; Junting Guo; Changchao She (Environmental Science and Pollution Research, 2022)

Study of salt migration on the upper part of the Great Wall under the rainfall-radiation cycle - Wenwu Chen; Haoxin Chen; Bobo Jia; Jun Bi; Xiang Li (Bulletin of Engineering Geology and the Environment, 2022)

Cross-generation trophic ecology of Dosidicus gigas in the eastern-central Pacific Ocean revealed from isotopic signatures in eye lenses - Guan Yu Hu; Zi Xin Wang; Bi Lin Liu; Meng Yao Huan; Xin Jun Chen (Fisheries Science, 2022)

PM2.5-bound phthalates and phthalate substitutes in a megacity of southern China: spatioseasonal variations, source apportionment, and risk assessment - Yu-Qi Huang; Yuan Zeng; Tao Wang; She-Jun Chen; Yu-Feng Guan; Bi-Xian Mai (Environmental Science and Pollution Research, 2022)

Changes in levels of legacy and emerging organophosphorus flame retardants and plasticizers in indoor dust from a former e-waste recycling area in South China: 2013–2017 - Bin Tang; Christina Christia; Xiao-Jun Luo; Adrian Covaci; Giulia Poma; Bi-Xian Mai (Environmental Science and Pollution Research, 2022)

Cassiterite oxygen isotopes in magmatic-hydrothermal systems: in situ microanalysis, fractionation factor, and applications - Yang Li; Sheng He; Rong-Qing Zhang; Xian-Wu Bi; Lian-Jun Feng; Guo-Qiang Tang; Wen-Zhong Wang; Fang Huang; Xian-Hua Li (Mineralium Deposita, 2022)

Transition in tectonic regime from the Paleo-Asian Ocean to Paleo-Pacific Ocean: constraints from the Jurassic adakitic and I-type granites, and calc-alkaline diorites at the northern margin of the North China Craton - Yan Jing; Wen-Chun Ge; Yu Dong; Hao Yang; Zheng Ji; Jun-Hui Bi; Hong-Ying Zhou; De-He Xing (International Geology Review, 2022)

Laboratory study on engineering geological characteristics of rocks within the fault - Kai Huang; Jiwen Wu; Yaoshan Bi; Jun Zhang (Arabian Journal of Geosciences, 2022)

A holobiont view of island biogeography: Unravelling patterns driving the nascent diversification of a Hawaiian spider and its microbial associates - Ellie E. Armstrong; Benoît Perez‐Lamarque; Ke Bi; Cerise Chen; Leontine E. Becking; Jun Ying Lim; Tyler Linderoth; Henrik Krehenwinkel; Rosemary G. Gillespie (Molecular Ecology, 2022)
The diversification of a host lineage can be influenced by both the external environment and its assemblage of microbes. Here, we use a young lineage of spiders, distributed along a chronologically arranged series of volcanic mountains, to investigate how their associated microbial communities have changed as the spiders colonized new locations. Using the stick spider Ariamnes waikula (Araneae, Theridiidae) on the island of Hawaiʻi, and outgroup taxa on older islands, we tested whether each component of the “holobiont” (spider hosts, intracellular endosymbionts and gut microbial communities) showed correlated signatures of diversity due to sequential colonization from older to younger volcanoes. To investigate this, we generated ddRAD data for the host spiders and 16S rRNA gene amplicon data from their microbiota. We expected sequential colonizations to result in a (phylo)genetic structuring of the host spiders and in a diversity gradient in microbial communities. The results showed that the host A . waikula is indeed structured by geographical isolation, suggesting sequential colonization from older to younger volcanoes. Similarly, the endosymbiont communities were markedly different between Ariamnes species on different islands, but more homogeneous among A . waikula populations on the island of Hawaiʻi. Conversely, the gut microbiota, which we suspect is generally environmentally derived, was largely conserved across all populations and species. Our results show that different components of the holobiont respond in distinct ways to the dynamic environment of the volcanic archipelago. This highlights the necessity of understanding the interplay between different components of the holobiont, to properly characterize its evolution.

Synthesis, characterization and antitumor mechanism investigation of ruthenium(II) polypyridyl complexes with artesunate moiety - Bi-Chun Chen; Jun-Jian Lu; Ning Jiang; Xiu-Rong Ma; Rong-Tao Li; Rui-Rong Ye (JBIC Journal of Biological Inorganic Chemistry, 2021)

Soil bacterial communities interact with silicon fraction transformation and promote rice yield after long-term straw return - Alin Song; Zimin Li; Yulin Liao; Yongchao Liang; Enzhao Wang; Sai Wang; Xu Li; Jingjing Bi; Zhiyuan Si; Yanhong Lu; Jun Nie; Fenliang Fan (Soil Ecology Letters, 2021)

Complement C3 Aggravates Post-epileptic Neuronal Injury Via Activation of TRPV1 - Guang-Tong Jiang; Lin Shao; Shuo Kong; Meng-Liu Zeng; Jing-Jing Cheng; Tao-Xiang Chen; Song Han; Jun Yin; Wan-Hong Liu; Xiao-Hua He; Yu-Min Liu; Lanzi Gongga; et al. (Neuroscience Bulletin, 2021)

Cysestermerol A, a rare stilbene sestermer with significant hypoglycemic activities from Cynodon dactylon - Feng Wang; Li Zhang; Bi-Jun Li; Qiu-Ming Liang; A-Li Chen; Zhen-Feng Fang; Shu-Mei Wang (Natural Product Research, 2021)

Sleep Characteristics and Cerebrospinal Fluid Progranulin in Older Adults: The CABLE Study - Meng Wang; Fu-Rong Sun; Yan-Lin Bi; Ya-Hui Ma; Jian-Jun Yin; Xue-Ning Shen; Xiao-Tong Wang; Lan Tan; Jin-Tai Yu (Neurotoxicity Research, 2021)

Seasonal variation of nitrogen biogeochemical processes constrained by nitrate dual isotopes in cascade reservoirs, Southwestern China - Sai-Nan Chen; Fu-Jun Yue; Xiao-Long Liu; Jun Zhong; Yuan-Bi Yi; Wan-Fa Wang; Yulin Qi; Hua-Yun Xiao; Si-Liang Li (Environmental Science and Pollution Research, 2021)

Investigating the spatial distribution of polychlorinated biphenyls in sediment in the Pearl River Delta, South China - Man-Ying Chen; Hong-Yin Liu; Xiao-Jun Luo; Bi-Xian Mai; Feng-Hui Lu (Environmental Monitoring and Assessment, 2021)

Effect of fine particle content on mechanical properties of tailings under high confining pressure - Qian Bi; Chang-hong Li; Jun-xin Chen (Arabian Journal of Geosciences, 2021)

Comparative study on virus shedding patterns in nasopharyngeal and fecal specimens of COVID-19 patients - Ning Zhang; Yuhuan Gong; Fanping Meng; Yi Shi; Jun Wang; Panyong Mao; Xia Chuai; Yuhai Bi; Penghui Yang; Fusheng Wang (Science China Life Sciences, 2021)

New titanite U–Pb and molybdenite Re–Os ages for a hydrothermal vein-type Cu deposit in the Lanping Basin, Yunnan, SW China: constraints on regional metallogeny and implications for exploration - Juan Li; Lei-Luo Xu; Xian-Wu Bi; Yong-Yong Tang; Xiang-Yuan Sheng; Hai-Jun Yu; Gong Liu; Rui Ma (Mineralium Deposita, 2021)

Middle–late permian I-type granitoids from the Diaobingshan region in the northern margin of the North China Craton: insight into southward subduction of the Paleo–Asian Ocean - Yan Jing; Zheng Ji; Wen-Chun Ge; Yu Dong; Hao Yang; Jun-Hui Bi (International Geology Review, 2021)

Quercetin alleviates neonatal hypoxic-ischemic brain injury by inhibiting microglia-derived oxidative stress and TLR4-mediated inflammation - Kai Le; Zhiping Song; Jie Deng; Xin Peng; Jun Zhang; Liang Wang; Lu Zhou; Haidi Bi; Zhengyu Liao; Zhen Feng (Inflammation Research, 2020)

Dietary lipid concentrations influence growth, body composition, morphology of the liver and mid-intestine, and antioxidant status of marbled eel (Anguilla marmorata) - Shi-Jun Chen; Peng Liu; You-Ming Jia; Hong-Ping Liao; Shao-Xuan Zhu; Li-Liu Zhou; Xue-Ming Dan; Li Liu; Jia-Hao Li; Su-Bi Zheng; Jun-Jiang Yang; Lian Gan (Aquaculture International, 2020)

Photosynthetic properties and biochemical metabolism of Cucurbita moschata genotypes following infection with powdery mildew - Bi-Hua Chen; Wei-Li Guo; He-Lian Yang; Qing-Fei Li; Jun-Guo Zhou; Xin-Zheng Li (Journal of Plant Pathology, 2020)
Powdery mildew (PM) is one of the most important fungal diseases in Cucurbita moschata (pumpkin) cultivation. This experiment was conducted to shed light on the physiological mechanisms of PM resistance in pumpkin cultivars. PM pathogen was inoculated on pumpkin seedlings, PM-susceptible genotype (JJJD) and PM-resistant genotype (inbred line 112–2) to study the PM-fungal growth, plant photosynthetic and biochemical parameters with different intervals of time. The disease index and pathogen growth observed for the PM-infected 112–2 seedlings were milder than those observed for the JJJD seedlings. The net photosynthetic rate (Pn), stomatal conductance (gs) and transpiration rate (Tr) were reduced for both the PM-infected genotypes, while the internal CO 2 concentration (Ci) increased in comparison with the non-infected controls. PM pathogen inoculation impaired the photosynthetic performance in seedlings of both genotypes and this was largely associated with stomatal closure. In comparison with the non-infected controls, the superoxide dismutase (SOD) and β-1,3-glucanase activities were reduced for both the PM-infected genotypes, while the peroxidase (POD) and phenylalanine ammonia lyase (PAL) activities were increased. The catalase (CAT) activity was reduced in the 112–2 genotype and increased in the JJJD genotype after PM pathogen inoculation. Together, our data show that PM resistance in pumpkin seedlings is associated with the maintenance of photosynthetic performance and the regulation of defense-related enzyme activities .

A novel mycovirus isolated from the plant-pathogenic fungus Alternaria dianthicola - Zhao Hu; Jun Guo; Bi Da Gao; Jie Zhong (Archives of Virology, 2020)

Transcriptome analysis reveals genes associated with leaf color mutants in Cymbidium longibracteatum - Jiang Yu; Wang Qiang; Shen Qin-Qin; Zhuo Bi-Ping; He Jun-Rong (Tree Genetics & Genomes, 2020)

Microneedle Array Patch (MAP) Consisting of Crosslinked Hyaluronic Acid Nanoparticles for Processability and Sustained Release - Dae-Sung Kim; Jun-Tae Choi; Cheong Bi Kim; Yu-Ra Shin; Pil-gu Park; Hyemi Kim; Jae Myun Lee; Jung-Hwan Park (Pharmaceutical Research, 2020)

The application of the ‘Gene-deletor’ technology in banana - Chun-hua Hu; Qiao-song Yang; Xiu-hong Shao; Tao Dong; Fang-cheng Bi; Chun-yu Li; Gui-ming Deng; Yi Li; Gan-jun Yi; Tong-xin Dou (Plant Cell, Tissue and Organ Culture (PCTOC), 2020)
Banana ( Musa spp.) is an important tropical crop. Banana industry is under biotic and abiotic stresses such as Fusarium wilt, typhoon, cold stress. Genetic engineering offers a powerful strategy to create germplasm of banana with enhanced resistance. The safety of genetically modified organisms has become a bottleneck restricting the popularization and application of genetically modified technology. In this study, a candidate promoter, LEAFY (LFY) for expression and flower initiation in Arabidopsis , was cloned and constructed to ‘Gene-deletor’ vector. Histochemical β-glucuronidase (GUS) staining results showed that the ‘Gene-deletor’ vector driven by LFY promoter could lead to 88.5% excision efficiency from Arabidopsis seeds based on more than 200 T 3 progeny examined per event. GUS staining was found to be partially negative in transgenic bananas, however, polymerase chain reaction could still detect the presence of large fragments of the vector. These results suggest that although LFY promoter could not completely drive the ‘Gene-deletor’ vector to achieve the effect of complete elimination of exogenous gene in bananas, its efficiency of eliminating exogenous gene laid a theoretical foundation for cloning banana fruit-specific promoters, that is, ‘non-transgenic’ GM bananas.

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Differential Transcriptomic and Metabolomic Responses in the Liver of Nile Tilapia (Oreochromis niloticus) Exposed to Acute Ammonia - Zong Xian Zhu; Dan Li Jiang; Bi Jun Li; Hui Qin; Zi Ning Meng; Hao Ran Lin; Jun Hong Xia (Marine Biotechnology, 2019)

The Characteristics of Climate Change and Adaptability Assessment of Migratory Bird Habitats in Wolonghu Wetlands - Jun Ma; Baisha Weng; Wuxia Bi; Dengming Yan; Meng Li; Ting Xu; Lina Wang; Lin Wang (Wetlands, 2019)

QTL Mapping for Red Blotches in Malaysia Red Tilapia (Oreochromis spp.) - Bi Jun Li; Zong Xian Zhu; Xiao Hui Gu; Hao Ran Lin; Jun Hong Xia (Marine Biotechnology, 2019)

Storage solution containing hydrogen improves the preservation effect of osteochondral allograft - Yunning Han; Pengwei Qu; Kaihong Zhang; Yikang Bi; Lu Zhou; Di Xie; Hongqiang Song; Jun Dong; Jianhong Qi (Cell and Tissue Banking, 2019)

Identifying a Long QTL Cluster Across chrLG18 Associated with Salt Tolerance in Tilapia Using GWAS and QTL-seq - Dan Li Jiang; Xiao Hui Gu; Bi Jun Li; Zong Xian Zhu; Hui Qin; Zi ning Meng; Hao Ran Lin; Jun Hong Xia (Marine Biotechnology, 2019)

Observational and model studies of synoptic current fluctuations in the Bohai Strait on the Chinese continental shelf - Yang Ding; Xianwen Bao; Zhigang Yao; Congcong Bi; Kai Wan; Min Bao; Zhipeng Jiang; Jun Song; Jia Gao (Ocean Dynamics, 2019)

Integrin-interacting protein Kindlin-2 induces mammary tumors in transgenic mice - Bing Li; Xiaochun Chi; Jiagui Song; Yan Tang; Juan Du; Xiaokun He; Xiaoran Sun; Zhenwu Bi; Yunling Wang; Jun Zhan; Hongquan Zhang (Science China Life Sciences, 2019)

Numerical investigation of effects of “baffles - deceleration strip” hybrid system on rock avalanches - Yu-zhang Bi; Si-ming He; Yan-jun Du; Jie Shan; Shuai-xing Yan; Dong-po Wang; Xin-po Sun (Journal of Mountain Science, 2019)

Full Thickness Skin Expansion ex vivo in a Newly Developed Reactor and Evaluation of Auto-Grafting Efficiency of the Expanded Skin Using Yucatan Pig Model - Man-Il Huh; Soo-Jin Yi; Kyung-Pil Lee; Hong Kyun Kim; Sang-Hyun An; Dan-Bi Kim; Rae-Hyung Ryu; Jun-Sik Kim; Jeong Ok Lim (Tissue Engineering and Regenerative Medicine, 2018)

In-time source tracking of watershed loads of Taihu Lake Basin, China based on spatial relationship modeling - Ce Wang; Jun Bi; Xu-Xiang Zhang; Qiang Fang; Yi Qi (Environmental Science and Pollution Research, 2018)

An integrated assessment of INDCs under Shared Socioeconomic Pathways: an implementation of C3IAM - Yi-Ming Wei; Rong Han; Qiao-Mei Liang; Bi-Ying Yu; Yun-Fei Yao; Mei-Mei Xue; Kun Zhang; Li-Jing Liu; Juan Peng; Pu Yang; Zhi-Fu Mi; Yun-Fei Du; et al. (Natural Hazards, 2018)

Identification of Strategic Residues at the Interface of Antigen–Antibody Interactions by In Silico Mutagenesis - Lu Xin; Hai Yu; Qiyang Hong; Xingjian Bi; Xiao Zhang; Zhiqing Zhang; Zhibo Kong; Qingbing Zheng; Ying Gu; Qinjian Zhao; Jun Zhang; Shaowei Li; et al. (Interdisciplinary Sciences: Computational Life Sciences, 2018)

Forecasting industrial water demand in Huaihe River Basin due to environmental changes - Xiao-jun Wang; Jian-yun Zhang; Shamsuddin Shahid; Shou-hai Bi; Amgad Elmahdi; Chuan-hua Liao; You-de Li (Mitigation and Adaptation Strategies for Global Change, 2018)

Molecular characterization of a putative gammapartitivirus in the phytopathogenic fungus Nigrospora oryzae - Jin Xiu Yu; Jun Zi Zhu; Ying Wang; Chao Jun Zhang; Jie Zhong; Hong Jian Zhu; Bi Da Gao; Qian Zhou (Archives of Virology, 2018)

Correction to: Engineered M13 Nanofiber Accelerates Ischemic Neovascularization by Enhancing Endothelial Progenitor Cells - Jun Hee Lee; Sung Wook Kim; Seung Taek Ji; Yeon Ju Kim; Woong Bi Jang; Jin-Woo Oh; Jaeho Kim; So Young Yoo; Sang Hong Baek; Sang-Mo Kwon (Tissue Engineering and Regenerative Medicine, 2018)

Identifying a Major QTL Associated with Salinity Tolerance in Nile Tilapia Using QTL-Seq - Xiao Hui Gu; Dan Li Jiang; Yan Huang; Bi Jun Li; Chao Hao Chen; Hao Ran Lin; Jun Hong Xia (Marine Biotechnology, 2018)

Significance of temperature and water availability for soil phosphorus transformation and microbial community composition as affected by fertilizer sources - Dasheng Sun; Qingfang Bi; Kejie Li; Peibin Dai; Yan Yu; Weiwei Zhou; Ting Lv; Xipeng Liu; Jun Zhu; Qichun Zhang; Chongwei Jin; Lingli Lu; et al. (Biology and Fertility of Soils, 2018)

Engineered M13 Nanofiber Accelerates Ischemic Neovascularization by Enhancing Endothelial Progenitor Cells - Jun Hee Lee; Sung Wook Kim; Seung Taek Ji; Yeon Ju Kim; Woong Bi Jang; Jin-Woo Oh; Jaeho Kim; So Young Yoo; Sang Hong Beak; Sang-Mo Kwon (Tissue Engineering and Regenerative Medicine, 2017)

Combined effects of soil heterogeneity, herbivory and detritivory on growth of the clonal plant Hydrocotyle vulgaris - Lu Liu; Peter Alpert; Bi-Cheng Dong; Jun-Min Li; Fei-Hai Yu (Plant and Soil, 2017)

The complete mitochondrial genome of a threatened loach (Beaufortia kweichowensis) and its phylogeny - Zheng-Yong Wen; Bi-Wen Xie; Chuan-Jie Qin; Jun Wang; Deng-Yue Yuan; Rui Li; Yuan-Chao Zou (Conservation Genetics Resources, 2017)

Two new stilbene trimers from Cynodon dactylon - Bi-Jun Li; Yao Liu; Ai-Tong Gu; Qing Zhang; Lei Chen; Shu-Mei Wang; Feng Wang (Natural Product Research, 2017)

Winogradskyella aurantia sp. nov., isolated from a marine solar saltern - Yue Sun; Bi-Yao Chen; Zong-Jun Du (Antonie van Leeuwenhoek, 2017)

Genome-Wide QTL Analysis Identified Significant Associations Between Hypoxia Tolerance and Mutations in the GPR132 and ABCG4 Genes in Nile Tilapia - Hong Lian Li; Xiao Hui Gu; Bi Jun Li; Chao Hao Chen; Hao Ran Lin; Jun Hong Xia (Marine Biotechnology, 2017)

Thermal ecology of three coexistent desert lizards: Implications for habitat divergence and thermal vulnerability - Shu-Ran Li; Yang Wang; Liang Ma; Zhi-Gao Zeng; Jun-Huai Bi; Wei-Guo Du (Journal of Comparative Physiology B, 2017)

Temporal changes of microRNA gga-let-7b and gga-let-7i expression in chickens challenged with subgroup J avian leukosis virus - Jun Ji; Huiqin Shang; Huanmin Zhang; Hongxin Li; Jingyun Ma; Yingzuo Bi; Qingmei Xie (Veterinary Research Communications, 2017)

Erratum to: Effects of elicitors on trichothecene accumulation and Tri genes expression in potato tubers inoculated with Fusarium sulphureum - Xue Hua-Li; Bi Yang; Zong Yuan-Yuan; Alejandro Calderón-Urrea; Wang Hu-Jun; Pu Lu-Mei; Wang Yi; Li Yong-Cai (European Journal of Plant Pathology, 2017)

mtDNA Heteroplasmy in Monozygotic Twins Discordant for Schizophrenia - Hong Li; Rui Bi; Yu Fan; Yong Wu; Yanqing Tang; Zongchang Li; Ying He; Jun Zhou; Jinsong Tang; Xiaogang Chen; Yong-Gang Yao (Molecular Neurobiology, 2017)

The Effect of Selenium on the Cd-Induced Apoptosis via NO-Mediated Mitochondrial Apoptosis Pathway in Chicken Liver - Runxiang Zhang; Ran Yi; Yanju Bi; Lu Xing; Jun Bao; Jianhong Li (Biological Trace Element Research, 2017)

Effects of elicitors on trichothecene accumulation and Tri genes expression in potato tubers inoculated with Fusarium sulphureum - Xue Hua-Li; Bi Yang; Zong Yuan-Yuan; Alejandro Calderón-Urrea; Wang Hu-Jun; Pu Lu-Mei; Wang Yi; Li Yong-Cai (European Journal of Plant Pathology, 2017)

Periodic increments in the jumbo squid (Dosidicus gigas) beak: a potential tool for determining age and investigating regional difference in growth rates - Bi Lin Liu; Xin Jun Chen; Yong Chen; Guan Yu Hu; Wei Yu; Jin Tao Wang; Jing Yuan Lin (Hydrobiologia, 2017)

TIMAP repression by TGFβ and HDAC3-associated Smad signaling regulates macrophage M2 phenotypic phagocytosis - Jun Yang; Shasha Yin; Fangfang Bi; Lin Liu; Tian Qin; Hongwei Wang; Wangsen Cao (Journal of Molecular Medicine, 2017)

Impacts of sediment type on the performance and composition of submerged macrophyte communities - Lin Liu; Xiang-Qi Bu; Jun-Yan Wan; Bi-Cheng Dong; Fang-Li Luo; Hong-Li Li; Fei-Hai Yu (Aquatic Ecology, 2017)

Copy Number Variations in Tilapia Genomes - Bi Jun Li; Hong Lian Li; Zining Meng; Yong Zhang; Haoran Lin; Gen Hua Yue; Jun Hong Xia (Marine Biotechnology, 2017)

Two new sesquiterpenoids produced by halophilic Nocardiopsis chromatogenes YIM 90109 - Ming-Wei Sun; Xiao-Mei Zhang; Hui-Li Bi; Wen-Jun Li; Chun-Hua Lu (Natural Product Research, 2017)

Low precipitation aggravates the impact of extreme high temperatures on lizard reproduction - Yang Wang; Zhi-Gao Zeng; Shu-Ran Li; Jun-Huai Bi; Wei-Guo Du (Oecologia, 2016)

A novel fusarivirus isolated from the phytopathogenic fungus Nigrospora oryzae - Jie Zhong; Si Qi Zhao; Gui Fang Li; Xi Dan Pang; Xiao Jun Deng; Hong Jian Zhu; Bi Da Gao; Qian Zhou (Virus Genes, 2016)

A R2R3-MYB transcription factor gene in common wheat (namely TaMYBsm1) involved in enhancement of drought tolerance in transgenic Arabidopsis - Meng-jun Li; Yu Qiao; Ya-qing Li; Zhan-liang Shi; Nan Zhang; Cai-li Bi; Jin-kao Guo (Journal of Plant Research, 2016)

Metastasis associated genomic aberrations in stage II rectal cancer - Hong Zhao; Zhi-Zhou Shi; Rui Jiang; Dong-Bing Zhao; Hai-Tao Zhou; Jian-Wei Liang; Xin-Yu Bi; Jian-Jun Zhao; Zhi-Yu Li; Jian-Guo Zhou; Zhen Huang; Ye-Fan Zhang; et al. (Genes & Genomics, 2016)

BAC mediated transgenic Large White boars with FSHα/β genes from Chinese Erhualian pigs - Pan Xu; Qiuyan Li; Kai Jiang; Qiang Yang; Mingjun Bi; Chao Jiang; Xiaopeng Wang; Chengbin Wang; Longyun Li; Chuanmin Qiao; Huanfa Gong; Yuyun Xing; et al. (Transgenic Research, 2016)

Spatial and Vertical Distribution of Dechlorane Plus in Mangrove Sediments of the Pearl River Estuary, South China - Yu-Xin Sun; Zai-Wang Zhang; Xiang-Rong Xu; Qin-Wei Hao; Yong-Xia Hu; Xiao-Bo Zheng; Xiao-Jun Luo; Zeng-Hui Diao; Bi-Xian Mai (Archives of Environmental Contamination and Toxicology, 2016)

Aquatic bioaccumulation and trophic transfer of tetrabromobisphenol-A flame retardant introduced from a typical e-waste recycling site - Lin Tao; Jiang-Ping Wu; Hui Zhi; Ying Zhang; Zi-He Ren; Xiao-Jun Luo; Bi-Xian Mai (Environmental Science and Pollution Research, 2016)

Identifying sources and hazardous risks of heavy metals in topsoils of rapidly urbanizing East China - Yang Liu; Zongwei Ma; Jianshu Lv; Jun Bi (Journal of Geographical Sciences, 2016)

Reconstructing cephalopod migration with statolith elemental signatures: a case study using Dosidicus gigas - Bi Lin Liu; Jie Cao; Samuel B. Truesdell; Yong Chen; Xin Jun Chen; Si Quan Tian (Fisheries Science, 2016)

Geo-engineered buffer capacity of two-layered absorbing system under the impact of rock avalanches based on Discrete Element Method - Yu-zhang Bi; Si-ming He; Xin-po Li; Yong Wu; Qiang Xu; Chao-jun Ouyang; Li-Jun Su; Hao Wang (Journal of Mountain Science, 2016)

Petrogenesis of Early Cretaceous volcanic rocks of the Manketouebo Formation in the Wuchagou region, central Great Xing’an Range, NE China, and tectonic implications: geochronological, geochemical, and Hf isotopic evidence - Zheng Ji; Wen-Chun Ge; Qing-Hai Wang; Hao Yang; Guo-Chun Zhao; Jun-Hui Bi; Yu Dong (International Geology Review, 2016)

TMDL development for the Taihu Lake’s influent rivers, China using variable daily load expressions - Ce Wang; Jun Bi (Stochastic Environmental Research and Risk Assessment, 2016)

A long-term investigation on microstructure of cement-stabilized handan clay - Honghua Zhao; Kun Zhou; Chunji Zhao; Bi-Wei Gong; Jun Liu (European Journal of Environmental and Civil Engineering, 2016)

Intranasal Delivery of Granulocyte Colony-Stimulating Factor Enhances Its Neuroprotective Effects Against Ischemic Brain Injury in Rats - Bao-liang Sun; Mei-qing He; Xiang-yu Han; Jing-yi Sun; Ming-feng Yang; Hui Yuan; Cun-dong Fan; Shuai Zhang; Lei-lei Mao; Da-wei Li; Zong-yong Zhang; Cheng-bi Zheng; et al. (Molecular Neurobiology, 2016)

Heavy metals in soils and road dusts in the mining areas of Western Suzhou, China: a preliminary identification of contaminated sites - Zongwei Ma; Kai Chen; Zhiyuan Li; Jun Bi; Lei Huang (Journal of Soils and Sediments, 2016)

Dehydroandrographolide enhances innate immunity of intestinal tract through up-regulation the expression of hBD-2 - Wen-Bi Xiong; Zhen-Jun Shao; Yao Xiong; Jian Chen; Yun Sun; Ling Zhu; Li-Ming Zhou (DARU Journal of Pharmaceutical Sciences, 2015)
Background Dehydroandrographolide (DA) is one of major active components in the well-known oriental herbal medicine Andrographis paniculata (Burm.f) Nees which belongs to the Acanthaceae family. DA is used for the treatment of infections in China. However, DA has not been found to significantly inhibit bacterial and viral growth directly. The current study investigates the effect of DA on the expression of human β –defensin-2 (hBD-2) in human intestinal epithelial cells and the possible signaling pathways. Methods Human intestinal epithelial HCT-116 cells were incubated with 1–100 μM DA for 2–24 h. RT–PCR and Western blot were used to assess the expression of hBD-2. The specific inhibitors were used and the levels of phosphorylation of signaling molecules were detected for dissecting the signaling pathways leading to the induction of hBD-2. Results MTT assay showed there was no obvious cytotoxicity for HCT-116 cells by 1–100 μM DA treatment. RT-PCR and Western blot assays showed that DA (1–100 μM) could up-regulate the expression of hBD-2, and the effect lasted longer than 24 h. By using SB203580 and SB202190 (inhibitors of p38), the enhancement of hBD-2 expression were significantly attenuated. However, inhibitor of ERK and inhibitor of JNK could not block the effect of DA. Furthermore, Western blot found activation of p38 but not ERK and JNK in DA-treated HCT-116 cells. Conclusion The results suggested that DA enhanced innate immunity of intestinal tract by up-regulating the expression of hBD-2 through the p38 MAPK pathways.

Erratum to: Characterization of Physa acuta expressed sequence tags and transcript mining following cadmium exposure - Ji Eun Jeong; Bharat Bhusan Patnaik; Se Won Kang; Hee-Ju Hwang; So Young Park; Tae Hun Wang; Eun Bi Park; Jae Bong Lee; Myung-Mo Nam; Yong Hun Jo; Yeon Soo Han; Jun-Sang Lee; et al. (Genes & Genomics, 2015)

Expressed sequence tag analysis and annotation of genetic information from the freshwater clam, Pisidium (Neopisidium) coreanum endemic to Korea - Ji Eun Jeong; Se Won Kang; Hee-Ju Hwang; So Young Park; Bharat Bhusan Patnaik; Changmu Kim; Soonok Kim; Myung-Mo Nam; Jae Bong Lee; Tae Hun Wang; Eun Bi Park; Sun Shin Yi; et al. (Genes & Genomics, 2015)

Characterization of Physa acuta expressed sequence tags and transcript mining following cadmium exposure - Ji Eun Jeong; Bharat Bhusan Patnaik; Se Won Kang; Hee-Ju Hwang; So Young Park; Tae Hun Wang; Eun Bi Park; Jae Bong Lee; Myung-Mo Nam; Yong Hun Jo; Yeon Soo Han; Jun-Sang Lee; et al. (Genes & Genomics, 2015)

Nontuberculous mycobacterial osteomyelitis - Sheng Bi; Fei-Shu Hu; Hai-Ying Yu; Kai-Jin Xu; Bei-Wen Zheng; Zhong-Kang Ji; Jun-Jie Li; Mei Deng; Hai-Yang Hu; Ji-Fang Sheng (Infectious Diseases, 2015)

Retraction Note to: Text mining and network analysis of molecular interaction in non-small cell lung cancer by using natural language processing - Jun Li; Lintao Bi; Yanxia Sun; Zhenxia Lu; Yumei Lin; Ou Bai; Hui Shao (Molecular Biology Reports, 2015)

Geographical distribution and risk assessment of persistent organic pollutants in golden threads (Nemipterus virgatus) from the northern South China Sea - Qing Hao; Yu-Xin Sun; Xiang-Rong Xu; Zi-Wei Yao; You-Shao Wang; Zai-Wang Zhang; Xiao-Jun Luo; Bi-Xian Mai (Ecotoxicology, 2015)

Determination of squid age using upper beak rostrum sections: technique improvement and comparison with the statolith - Bi Lin Liu; Xin Jun Chen; Yong Chen; Guan Yu Hu (Marine Biology, 2015)

Bioaccumulative characteristics of tetrabromobisphenol A and hexabromocyclododecanes in multi-tissues of prey and predator fish from an e-waste site, South China - Bin Tang; Yan-Hong Zeng; Xiao-Jun Luo; Xiao-Bo Zheng; Bi-Xian Mai (Environmental Science and Pollution Research, 2015)

Spatial difference in elemental signatures within early ontogenetic statolith for identifying Jumbo flying squid natal origins - Bi Lin Liu; Yong Chen; Xin Jun Chen (Fisheries Oceanography, 2015)
Signatures of trace elements and isotopes in the parts of hard structures formed in the early ontogenetic stages can be used as potential natural tags of adult cephalopods to trace their origins. The Jumbo flying squid, Dosidicus gigas , is widely distributed in the eastern Pacific Ocean. Fourteen detected elemental signatures ( 7 Li, 23 Na, 24 Mg, 39 K, 43 Ca 55 Mn, 59 Co, 60 Ni, 63 Cu, 66 Zn, 88 Sr, 137 Ba, 208 Pb and 238 U) were determined in the nuclear zone (N), representing the embryonic stage, and the postnuclear zone ( PN ), representing the paralarval stage of statoliths for adult D. gigas collected off the Costa Rican, Peruvian and Chilean Exclusive Economic Zones ( EEZ s) using laser ablation inductively coupled plasma mass spectrometry ( LA ‐ ICP ‐ MS ). All measured signatures were significantly different between embryonic and paralarval statoliths, except for Sr, Ba and Pb. Over the three regions, a significant difference was found for Na and Ba within embryonic statoliths and Zn and Ba within paralarval statoliths. A high Ba/Ca ratio in statoliths obtained from Costa Rica was because of the prevalence of strong upwelling in the area. Elemental signatures, especially Ba/Ca, in early ontogenetic statoliths could be used as a proxy for distinguishing different geographical groups and identifying natal origins. However, elemental signatures in embryonic statoliths tended to be a better natural tag than those in paralarval statoliths indicating that paralarvae with the same origin had distinct dispersal pathways. Additionally, stepwise discriminant analysis ( SDA ) showed there were at least two migration‐based groups: ‘northern’ and ‘southern’ in the eastern Pacific Ocean. Overall, the derived results can improve our knowledge of the population structure, connectivity and life history of D. gigas .

TaUBA, a UBA domain-containing protein in wheat (Triticum aestivum L.), is a negative regulator of salt and drought stress response in transgenic Arabidopsis - Xiao Li; Shuang-shuang Zhang; Jun-xia Ma; Guang-yan Guo; Xue-yong Zhang; Xu Liu; Cai-li Bi (Plant Cell Reports, 2015)

A potential anticancer agent 1,2-di(quinazolin-4-yl)diselane induces apoptosis in non-small-cell lung cancer A549 cells - Yinjiu Huang; Xiaomei Hu; Gang Liu; Hao Liu; Jianguo Hu; Zhenzhong Feng; Bi Tang; Jun Qian; Qiyi Wang; Yuyuan Zhang; Yanan Pu (Medicinal Chemistry Research, 2015)

Application of Hilbert-Huang Transform to the analysis of the landslides triggered by the Wenchuan earthquake - Chang-wei Yang; Jian-jing Zhang; Jun-wei Bi (Journal of Mountain Science, 2015)

Association of soil arsenic and nickel exposure with cancer mortality rates, a town-scale ecological study in Suzhou, China - Kai Chen; Qi Lin Liao; Zong Wei Ma; Yang Jin; Ming Hua; Jun Bi; Lei Huang (Environmental Science and Pollution Research, 2015)

Land subsidence in the modern Yellow River Delta based on InSAR time series analysis - Jin-Zhi Zhang; Hai-jun Huang; Hai-bo Bi (Natural Hazards, 2015)

Molecular characterization of a novel reovirus isolated from Pekin ducklings in China - Ying-Qi Zhu; Chuan-Feng Li; Zhuang-Li Bi; Zong-Yan Chen; Chun-Chun Meng; Gui-Jun Wang; Chan Ding; Guang-Qing Liu (Archives of Virology, 2015)

RETRACTED ARTICLE: Text mining and network analysis of molecular interaction in non-small cell lung cancer by using natural language processing - Jun Li; Lintao Bi; Yanxia Sun; Zhenxia Lu; Yumei Lin; Ou Bai; Hui Shao (Molecular Biology Reports, 2014)

Detection and sequence analysis of two novel co-infecting double-strand RNA mycoviruses in Ustilaginoidea virens - Jie Zhong; Xiang Hua Lei; Jun Zi Zhu; Ge Song; Ya Dong Zhang; Yi Chen; Bi Da Gao (Archives of Virology, 2014)

Evaluation and source identification of trace element contamination of soils in the Qixia lead-zinc mining area, Jiangsu, China - Zongwei Ma; Tiantian Li; Changsheng Qu; Jun Bi; Lei Huang (Journal of Soils and Sediments, 2014)

Species-Specific Bioaccumulation of Halogenated Organic Pollutants and Their Metabolites in Fish Serum from an E-Waste Site, South China - Yan-Hong Zeng; Xiao-Jun Luo; Xiao-Bo Zheng; Bin Tang; Jiang-Ping Wu; Bi-Xian Mai (Archives of Environmental Contamination and Toxicology, 2014)

The comparison analysis of Chinese public perception of earthquakes on different time scales - Lei Huang; Weiliang Bao; Kai Chen; Jun Bi (Natural Hazards, 2014)

Occurrence, sources, and ecological risks of PBDEs, PCBs, OCPs, and PAHs in surface sediments of the Yangtze River Delta city cluster, China - Ting Zhang; Wen-Long Yang; She-Jun Chen; Dian-Long Shi; Hu Zhao; Yi Ding; Ye-Ru Huang; Nan Li; Yue Ren; Bi-Xian Mai (Environmental Monitoring and Assessment, 2014)

Improvement of pseudo-static method for slope stability analysis - Chang-wei Yang; Jian-jing Zhang; Xiao Fu; Chuan-bin Zhu; Jun-wei Bi (Journal of Mountain Science, 2014)

Nrf2 expression participates in growth and differentiation of endometrial carcinoma cells in vitro and in vivo - Kainan Li; Chen Zhong; Baocheng Wang; Jun He; Jingwang Bi (Journal of Molecular Histology, 2014)

Complete genome sequence and organization of a novel virus from the rice false smut fungus Ustilaginoidea virens - Jie Zhong; Jun-Zi Zhu; Xiang-Hua Lei; Dan Chen; Hong-Jian Zhu; Bi-Da Gao (Virus Genes, 2014)

Vibrio harveyi as a causative agent of mass mortalities of megalopa in the seed production of swimming crab Portunus trituberculatus - Xiao-Jun Zhang; Xue-Song Bai; Bin-Lun Yan; Ke-Ran Bi; Lei Qin (Aquaculture International, 2014)

Contribution of arbuscular mycorrhizal fungi to the development of maize (Zea mays L.) grown in three types of coal mine spoils - Wei Guo; Renxin Zhao; Ruiying Fu; Na Bi; Lixin Wang; Wenjing Zhao; Jiangyuan Guo; Jun Zhang (Environmental Science and Pollution Research, 2014)

Sex identification and genetic variation of Saccharina (Phaeophyta) gametophytes as revealed by inter-simple sequence repeat (ISSR) markers - Jun-Gang Gu; Yu-Ping Sun; Yu Liu; Yan-Hui Bi; Zhi-Gang Zhou (Journal of Applied Phycology, 2014)

Phosphorus loads from different urban storm runoff sources in southern China: a case study in Wenzhou City - Dong Zhou; Chun-Juan Bi; Zhen-Lou Chen; Zhong-Jie Yu; Jun Wang; Jing-Chao Han (Environmental Science and Pollution Research, 2013)

Purification of contaminated paddy fields by clean water irrigation over two decades - Yiping Tai; Huanping Lu; Zhian Li; Ping Zhuang; Bi Zou; Hanping Xia; Faming Wang; Gang Wang; Jun Duan; Jianxia Zhang (Environmental Geochemistry and Health, 2013)

Quantifying Phosphorus Flow Pathways Through Socioeconomic Systems at the County Level in China - Jun Bi; Qinqin Chen; Ling Zhang; Zengwei Yuan (Journal of Industrial Ecology, 2013)
Summary Phosphorus (P) is a key factor in aquatic eutrophication, and P contamination has become a common issue worldwide. Many developing countries, including China, have made great efforts in the anti‐P contamination battle. In this article we mainly discuss the P flow in Wuwei, a typical county in China with insufficient wastewater treatment, using the method of static substance flow analysis. We show that characterizing P metabolic pathways and flows at the county level can provide useful information about P pollution. Through complex calculations, we found that Wuwei County released 3,552 metric tons (t) of P into the local aquatic environment in 2008 and that its P load (3.35 kilograms P per capita per year [kg P/cap/yr] or 19.43 kilograms P per hectare per year [kg‐P/ha/yr]) was greater than both the adjoining counties’ and Chaohu City's average levels combined. The agricultural subsystem discharged the largest quantity of P (2,572 t) and had a relatively low production conversion efficiency (32%) and P waste recycling rate (36%). The rural residential and small‐scale livestock breeding systems also accounted for substantial portions of P discharge. Anti‐P contamination efforts should consequently focus on those three subsystems. Based on the results of this case study, we also discuss the feasibility of potential efforts to reduce P contamination.

Spatial distribution and ecotoxicological risk assessment of heavy metals in surface sediments of the southern Bohai Bay, China - Bangqi Hu; Guogang Li; Jun Li; Jianqiang Bi; Jingtao Zhao; Ruyuan Bu (Environmental Science and Pollution Research, 2013)

Understanding the Price Dynamics in the Jiangsu SO2 Emissions Trading Program in China: A Multiple Periods Analysis - Yuanchun Zhou; Yueying Wu; Bing Zhang; Jun Bi (Environmental Modeling & Assessment, 2013)

Multi-angle Indicators System of Non-point Pollution Source Assessment in Rural Areas: A Case Study Near Taihu Lake - Lei Huang; Jie Ban; Yu Ting Han; Jie Yang; Jun Bi (Environmental Management, 2013)

Modeling Nutrient Release in the Tai Lake Basin of China: Source Identification and Policy Implications - Beibei Liu; Heng Liu; Bing Zhang; Jun Bi (Environmental Management, 2013)

Dynamic distribution and tissue tropism of infectious laryngotracheitis virus in experimentally infected chickens - Lin-Guo Wang; Jun Ma; Chun-Yi Xue; Wei Wang; Chao Guo; Feng Chen; Jian-Ping Qin; Ning-Hai Huang; Ying-Zuo Bi; Yong-Chang Cao (Archives of Virology, 2013)

Exon 47 skipping of fibrillin-1 leads preferentially to cardiovascular defects in patients with thoracic aortic aneurysms and dissections - Wen-Jing Wang; Peili Han; Jun Zheng; Fang-Yuan Hu; Yun Zhu; Jin-Sheng Xie; Jian Guo; Zhe Zhang; Jie Dong; Gu-Yan Zheng; Huiqing Cao; Tian-Shu Liu; et al. (Journal of Molecular Medicine, 2013)

Lymphatic microvessel density and vascular endothelial growth factor-C and -D as prognostic factors in breast cancer: a systematic review and meta-analysis of the literature - Jun Wang; Yan Guo; Baocheng Wang; Jingwang Bi; Kainan Li; Xiuju Liang; Huili Chu; Huihui Jiang (Molecular Biology Reports, 2012)

Effects of indole-3-acetic acid and auxin transport inhibitors on the style curvature of three Alpinia species (Zingiberaceae) - Yin-Ling Luo; Ting-Ju Bi; Dong Li; Zhi-Long Su; Chuan Tao; Yan-Jiang Luo; Qing-Jun Li (Acta Physiologiae Plantarum, 2012)

Molybdenite Re–Os and muscovite 40Ar/39Ar dating of quartz vein-type W–Sn polymetallic deposits in Northern Guangdong, South China - Hua-Wen Qi; Rui-Zhong Hu; Xiao-Fei Wang; Wen-Jun Qu; Xian-Wu Bi; Jian-Tang Peng (Mineralium Deposita, 2012)

Phylogenetic analysis of hemagglutinin genes of 40 H9N2 subtype avian influenza viruses isolated from poultry in China from 2010 to 2011 - Feng Chen; Zhuan-Qiang Yan; Jun Liu; Jun Ji; Shuang Chang; Di Liu; Jian-Ping Qin; Jing-Yun Ma; Ying-Zuo Bi; Qing-Mei Xie (Virus Genes, 2012)

Identification of Trace Organic Pollutants in Drinking Water and the Associated Human Health Risks in Jiangsu Province, China - Bing Li; Changsheng Qu; Jun Bi (Bulletin of Environmental Contamination and Toxicology, 2012)

Lymphatic microvessel density as a prognostic factor in non-small cell lung carcinoma: a meta-analysis of the literature - Jun Wang; Kainan Li; Baocheng Wang; Jingwang Bi (Molecular Biology Reports, 2012)

Has-miR-146a polymorphism (rs2910164) and cancer risk: a meta-analysis of 19 case–control studies - Jun Wang; Jingwang Bi; Xin Liu; Kainan Li; Jianshi Di; Baocheng Wang (Molecular Biology Reports, 2012)

Deletion of RBP-J in adult mice leads to the onset of aortic valve degenerative diseases - Zhi Li; Lei Feng; Chun-Mei Wang; Qi-Jun Zheng; Bi-Jun Zhao; Wei Yi; Jin-Zhou Zhang; Yue-Min Wang; Hai-Tao Guo; Ding-Hua Yi; Hua Han (Molecular Biology Reports, 2012)

Estimation of Copper In‐use Stocks in Nanjing, China - Ling Zhang; Zengwei Yuan; Jun Bi (Journal of Industrial Ecology, 2012)
Summary Copper (Cu) is an essential but supply‐restricted resource in China. Characterization of in‐use stocks can provide useful instruction for the future recycling of copper. This article attempts to estimate copper in‐use stocks in a Chinese city. To this purpose, an extensive bottom‐up estimate of copper stocks in use in Nanjing in the year 2009 was conducted. The results are a total stock estimate of 295 gigagrams (Gg) of copper or 46.9 kilograms (kg) of copper per capita for 2009. Infrastructure, equipment, and buildings contain 42.0%, 26.1%, and 28.1% of the total stock, respectively, indicating that these three categories are principal potential reservoirs of a secondary copper resource. The copper in transportation amounts to only about 3.7% of the total amount. The per capita stock was compared with similar studies carried out in other regions of the world, and the results show that the Nanjing level is significantly lower than developed countries. On the whole, our results show that electric power transmission and distribution systems, buildings, household durables, and industrial equipment are the four largest potential reservoirs of copper scrap.

miR-29a and miR-142-3p downregulation and diagnostic implication in human acute myeloid leukemia - Fang Wang; Xiao-Shuang Wang; Gui-Hua Yang; Peng-Fei Zhai; Zhen Xiao; Liang-Yu Xia; Li-Rong Chen; Yu Wang; Xiao-Zhong Wang; Lai-Xi Bi; Nian Liu; Yang Yu; et al. (Molecular Biology Reports, 2012)

PEMT G523A (V175M) Is Associated with Sporadic Alzheimer's Disease in a Chinese Population - Xiu-Hua Bi; Hua-Lu Zhao; Zhen-Xin Zhang; Jun-Wu Zhang (Journal of Molecular Neuroscience, 2012)

Erratum to: Life cycle energy consumption and CO2 emission of an office building in China - Huijun Wu; Zengwei Yuan; Ling Zhang; Jun Bi (The International Journal of Life Cycle Assessment, 2012)

Life cycle energy consumption and CO2 emission of an office building in China - Huijun J. Wu; Zengwei W. Yuan; Ling Zhang; Jun Bi (The International Journal of Life Cycle Assessment, 2012)

Analysis of indica- and japonica-specific markers of Oryza sativa and their applications - Xiao-Jun Dai; Yuan-Zhu Yang; Liang Zhou; Li-Jun Ou; Man-Zhong Liang; Wen-Jia Li; Gong-Ping Kang; Liang-Bi Chen (Plant Systematics and Evolution, 2012)

Permissible Value for Vanadium in Allitic Udic Ferrisols Based on Physiological Responses of Green Chinese Cabbage and Soil Microbes - Xi-yuan Xiao; Miao Yang; Zhao-hui Guo; Yue-ping Luo; Jun-ping Bi (Biological Trace Element Research, 2012)

Characterization of a new male sterility-related gene Camf1 in Capsicum annum L. - Chang Ming Chen; Xue Feng Hao; Guo Ju Chen; Bi Hao Cao; Qing Hua Chen; Shao Qun Liu; Jian Jun Lei (Molecular Biology Reports, 2012)

Curcumin promotes cholesterol efflux from adipocytes related to PPARgamma–LXRalpha–ABCA1 passway - Shao-zhuang Dong; Shui-ping Zhao; Zhi-hong Wu; Jun Yang; Xiang-zhu Xie; Bi-lian Yu; Sai Nie (Molecular and Cellular Biochemistry, 2011)

Heavy Metals in Hair of Residents in an E-Waste Recycling Area, South China: Contents and Assessment of Bodily State - Jing Zheng; Xiao-Jun Luo; Jian-Gang Yuan; Luo-Yiyi He; Yi-Hui Zhou; Yong Luo; She-Jun Chen; Bi-Xian Mai; Zhong-Yi Yang (Archives of Environmental Contamination and Toxicology, 2011)

Clinical outcomes of fertility-sparing treatments in young patients with epithelial ovarian carcinoma - Jun Hu; Li-rong Zhu; Zhi-qing Liang; Yuan-guang Meng; Hong-yan Guo; Peng-peng Qu; Cai-ling Ma; Cong-jian Xu; Bi-bo Yuan (Journal of Zhejiang University-SCIENCE B, 2011)

Tissue-specific and expression of porcine growth hormone gene in BAC transgenic mice - Jia Tong; Simon G. Lillico; Ming Jun Bi; Tong Qing; Xiao Fang Liu; YuanYuan Wang; Min Zheng; Meili Wang; Yun Ping Dai; C. Bruce A. Whitelaw; Ning Li (Transgenic Research, 2011)

Genetic differentiation of wild and hatchery Oujiang color common carp: potential application to the identification of escapees - Yuqing Ma; Chenghui Wang; Jun Wang; Xinxin Yang; Xiang Bi; Lihua Xu (Fisheries Science, 2011)

Isolation and expression analysis of LEA genes in peanut (Arachis hypogaea L.) - Lei Su; Chuan-Zhi Zhao; Yu-Ping Bi; Shu-Bo Wan; Han Xia; Xing-Jun Wang (Journal of Biosciences, 2011)

Polychlorinated biphenyls and organochlorinated pesticides in birds from a contaminated region in South China: association with trophic level, tissue distribution and risk assessment - Xiu-Lan Zhang; Xiao-Jun Luo; Juan Liu; Yong Luo; She-Jun Chen; Bi-Xian Mai (Environmental Science and Pollution Research, 2011)

Screening Level of PAHs in Sediment Core from Lake Hongfeng, Southwest China - Jian-Yang Guo; Feng-Chang Wu; Liang Zhang; Hai-Qing Liao; Run-Yu Zhang; Wei Li; Xiao-Li Zhao; She-Jun Chen; Bi-Xian Mai (Archives of Environmental Contamination and Toxicology, 2011)

Mineral status and mechanical properties of cancellous bone exposed to hydrogen peroxide for various time periods - Dan Li; Long Bi; Guolin Meng; Jun Wang; Rong Lv; Min Liu; Jian Liu; Yunyu Hu (Cell and Tissue Banking, 2011)

Synthesis, structure characterization, and biological evaluation of some new 1,2,3-benzotriazole derivatives - Jun Wan; Xia Yan; Cuiping Ma; Sai Bi; Hai-Liang Zhu (Medicinal Chemistry Research, 2010)

Polybrominated Diphenyl Ethers (PBDEs), Polychlorinated Biphenyles (PCBs), Hydroxylated and Methoxylated-PBDEs, and Methylsulfonyl-PCBs in Bird Serum from South China - Juan Liu; Xiao-Jun Luo; Le-Huan Yu; Ming-Jing He; She-Jun Chen; Bi-Xian Mai (Archives of Environmental Contamination and Toxicology, 2010)

Characterization of Five Putative Acyl Carrier Protein (ACP) Isoforms from Developing Seeds of Arachis hypogaea L. - Meng-Jun Li; Xing-Jun Wang; Lei Su; Yu-Ping Bi; Shu-Bo Wan (Plant Molecular Biology Reporter, 2010)

Induction of apoptosis in hepatocellular carcinoma Smmc-7721 cells by vitamin K2 is associated with p53 and independent of the intrinsic apoptotic pathway - Lu Li; Zhiling Qi; Jin Qian; Fuyong Bi; Jun Lv; Lei Xu; Ling Zhang; Hongyu Chen; Renbing Jia (Molecular and Cellular Biochemistry, 2010)

A method for generating precise gene deletions and insertions in Escherichia coli - Qi-Ming Zhou; Dong-Jie Fan; Jiang-Bi Xie; Chuan-Peng Liu; Jun-Mei Zhou (World Journal of Microbiology and Biotechnology, 2010)

Public Perception of Blue-Algae Bloom Risk in Hongze Lake of China - Lei Huang; Kai Sun; Jie Ban; Jun Bi (Environmental Management, 2010)

Expression and characterization of Momordica Chanrantia anti-hyperglycaemic peptide in Escherichia coli - Si-Xiu Liu; Zhong-Ping Fu; Rui-Min Mu; Zhi-Bi Hu; Fu-Jun Wang; Xiang-Rong Wang (Molecular Biology Reports, 2010)

Expression and characterization of two domains of Pinellia ternata agglutinin (PTA), a plant agglutinin from Pinellia ternata with antifungal activity - Li-Jun Ling; Yan-Zhuo Yang; Yu-Rong Bi (World Journal of Microbiology and Biotechnology, 2010)

Isolation and Characterization of Putative Acetyl-CoA Carboxylases in Arachis hypogaea L. - Meng-Jun Li; Han Xia; Chuan-Zhi Zhao; Ai-Qin Li; Chang-Sheng Li; Yu-Ping Bi; Shu-Bo Wan; Xing-Jun Wang (Plant Molecular Biology Reporter, 2010)

Increasing polybrominated diphenyl ether (PBDE) contamination in sediment cores from the inner Clyde Estuary, UK - Christopher H. Vane; Yun-Juan Ma; She-Jun Chen; Bi-Xian Mai (Environmental Geochemistry and Health, 2010)

Acute respiratory distress syndrome induced by H9N2 virus in mice - Guangcun Deng; Jianmin Bi; Fuli Kong; Xuezhu Li; Qiang Xu; Jun Dong; Miaojie Zhang; Lihong Zhao; Zhihua Luan; Nana Lv; Jian Qiao (Archives of Virology, 2010)

The mixture of procyanidins extracted from the lotus seed pod and bilobalide ameliorates scopolamine-induced memory impairment in mice - Li Zhang; Ji-Qu Xu; Shuang Rong; Bi-Jun Xie; Zhi-Da Sun; Yun-Jian Zhang; Lie-Gang Liu (Neuroscience Bulletin, 2009)

Cloning and sequence analysis of putative type II fatty acid synthase genes from Arachis hypogaea L. - Meng-Jun Li; Ai-Qin Li; Han Xia; Chuan-Zhi Zhao; Chang-Sheng Li; Shu-Bo Wan; Yu-Ping Bi; Xing-Jun Wang (Journal of Biosciences, 2009)

Generation and characterisation of Tn5-tagged Xanthomonas oryzae pv. oryzae mutants that overcome Xa23-mediated resistance to bacterial blight of rice - Chun-Lian Wang; An-Bi Xu; Ying Gao; Ying-Lun Fan; Yun-Tao Liang; Chong-Ke Zheng; Liang-Qing Sun; Wen-Quan Wang; Kai-Jun Zhao (European Journal of Plant Pathology, 2009)

Optimizing the shoot proliferation protocol of Penthorum chinense by axillary buds - Li-Qiang Wang; Jun Yang; E. Deng; Guang-Bi Wang; Zheng-Song Peng (Biotechnology Letters, 2008)

Induction of diploid gynogenesis in turbot Scophthalmus maximus with left-eyed flounder Paralichthys olivaceus sperm - Jian-He Xu; Feng You; Wei Sun; Bin-Lun Yan; Pei-Jun Zhang; Bi-Xiang Jing (Aquaculture International, 2008)

Distribution and partition of polycyclic aromatic hydrocarbon in surface water of the Pearl River Estuary, South China - Xiao-Jun Luo; Bi-Xian Mai; Qing-Shu Yang; She-Jun Chen; Eddy Y. Zeng (Environmental Monitoring and Assessment, 2008)

Long-term culture of keratinocyte-like cells derived from mouse embryonic stem cells - Hai-Jun Huang; Qi-Shuang Gao; Bi-Fei Tao; Si-Wen Jiang (In Vitro Cellular & Developmental Biology - Animal, 2008)

Molecular mechanism underlying differential apoptosis between human melanoma cell lines UACC903 and UACC903(+6) revealed by mitochondria-focused cDNA microarrays - Qiuyang Zhang; Jun Wu; AnhThu Nguyen; Bi-Dar Wang; Ping He; Georges St. Laurent; Owen M. Rennert; Yan A. Su (Apoptosis, 2008)

Distribution, Source Apportionment, and Transport of PAHs in Sediments from the Pearl River Delta and the Northern South China Sea - Xiao-Jun Luo; She-Jun Chen; Bi-Xian Mai; Guo-Ying Sheng; Jia-Mo Fu; Eddy Y. Zeng (Archives of Environmental Contamination and Toxicology, 2008)

Partial characterization of a hydrophobin protein Po.HYD1 purified from the oyster mushroom Pleurotus ostreatus - Ai Min Ma; Lin Jun Shan; Hui Jie Wang; Zhao Ping Du; Bi Jun Xie (World Journal of Microbiology and Biotechnology, 2008)

Association of NAD(P)H:Quinone Oxidoreductase 1 Polymorphism and Alzheimer’s Disease in Chinese - Jian-Tao Bian; Hua-Lu Zhao; Zhen-Xin Zhang; Xiu-Hua Bi; Jun-Wu Zhang (Journal of Molecular Neuroscience, 2008)

A myxobacterium strain Sorangium cellulosum AHB125 producing epothilone B and other anticancer substances - Wen-Jie Guo; Guan-Jun Tao; Wen-Yi Tao; Feng-Jie Cui; Xian-Chun Jin; Fang Bi; Zheng-Hong Xu; Zong-Hua Ao (Natural Product Research, 2007)

Effects of osmotic stress on antioxidant enzymes activities in leaf discs of PSAG12-IPT modified gerbera - Qi-xian Lai; Zhi-yi Bao; Zhu-jun Zhu; Qiong-qiu Qian; Bi-zeng Mao (Journal of Zhejiang University-SCIENCE B, 2007)

The Circular Economy: A New Development Strategy in China - Zengwei Yuan; Jun Bi; Yuichi Moriguichi (Journal of Industrial Ecology, 2006)